Low-temperature stress reshapes hepatic metabolic profiles in cultured Epinephelus akaara - Jichun Li; Rui Zhao; Hongling Ping; Tao Zhang; Huilai Shi; Longbo Gao; Bin Lu; Bin Li; Yingying Ye; Jiji Li; Jianshe Zhang (Aquaculture, 2027)

Investigating frozen strength characteristics and their relationship with microscopic pore structure of chloride silty clay improved by cement - Ya Lu; Ting Zhang; Ping Yang; Lin Li; Ming Zhong; Yaqin Zhang; Xin Shi (European Journal of Environmental and Civil Engineering, 2026)

Functional characterization of CnAGAL2, a key α-galactosidase involved in postharvest endosperm thickening of coconut (Cocos nucifera L.) - Jian Wang; Fan-jing Zhang; Fang Liu; Yu-ping Man; Shi-biao Liu; Yan-chang Wang; Dong-dong Li (Postharvest Biology and Technology, 2026)

Endometriosis-derived exosomal MicroRNA-125b-5p downregulates phosphatidylinositol 3-Kinase/Protein Kinase B signaling pathways via vascular endothelial growth factor to decelerate endometriosis progression - Lei Zhang; Litong Zhu; Huangjin Luo; Xiaolin Chen; Guiyuan Yu; Qiuxia Li; Mo Chen; Ping Jin; Qiuling Shi (Molecular Biology Reports, 2026)

PSMG3 enhances the proliferation and metastasis of hepatocellular carcinoma via inhibiting HDAC6 - Shuaihui Wu; Caiyan Wu; Huibin Wang; Yang Shi; Ping Jiang; Dilinigeer Tayier; Kunlei Wang; Qian Cheng; Xinyin Li; Qifeng Wei; Zhixiang Cheng; Bo Liao; et al. (Functional & Integrative Genomics, 2026)

No-tillage straw mulching alters fallow rainfall use and improves long-term water balance and yield stability of winter wheat: A 38-year simulation on the Loess Plateau - Xinrui Shi; Chao Li; Chen Cui; Ping Li; Yuzheng Zong; Dongsheng Zhang; Zhiqiang Gao; Xingyu Hao (Agricultural Systems, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Analytical modeling for uplift resistance of subsea pipelines in loose sand: Local flow-around failure mechanism and smooth-pipe validation - Xiao-Mi Li; Yu-Min Shi; Ning Wang; Xiao-Bing Lu; Fu-Ping Gao (Ocean Engineering, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Cytokinin represses NH4+ efflux by suppressing GH3.5 transcription through an ARR10/12-dependent pathway - Ting-Ting Li; Chi-Shang Luan; Li Zhang; Meng Wang; Herbert J. Kronzucker; Chuan-Fa Liu; Ping Lan; Yunqi Liu; Weiming Shi; Dong-Wei Di (Journal of Plant Physiology, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Erosion and entrainment in dry granular flows: Insights from large-scale experiments - Shi-lin Zhang; Yang Gao; Yue-ping Yin; Lonneke Roelofs; Wen-pei Wang; Xie-wen Hu; Bin Li (Engineering Geology, 2026)

Systemic metabolic rebalance and regulatory network reconstruction drive high-yield production of sucrose isomerase by nutrient deficient Bacillus amyloliquefaciens - Maojun Wang; Yifan Tong; Ling Ping; Ramon Gonzalez; Aiqin Shi; Yu Li; Fuping Lu (Chemical Engineering Journal, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Straw mulching mitigates warming-induced yield loss and leverages elevated CO2 to improve winter wheat productivity under projected climate scenarios - Qi Yang; Xiaoran Chen; Zixuan Wang; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Zhiqiang Gao; Ping Li; Xingyu Hao (Agricultural and Forest Meteorology, 2026)

Pesticide exposure in Eriocheir sinensis: Oxidative stress, endocrine disruption, gut–hepatopancreas axis impairment, and systems toxicology - Shi-Rong Li; Dan-Dan Bian; Xiang Lu; Shuang-Gui Dai; Bo-Ping Tang; Qiu-Ning Liu (Pesticide Biochemistry and Physiology, 2026)

Trace element sources, migration and health risks associated with river-groundwater interaction: Insights from isotopes, fluorescence spectroscopy and Monte Carlo simulation - Xu Yang; Muhan Li; Yiying Miao; Fuyang Huang; Zeyuan Liu; Hongli Ma; Ping Miao; Jigang Shi; Zengbao Zhang; Shen Qu; Ruihong Yu (Journal of Hydrology, 2026)

Effect of chitosan on the quality of spinach puree during freezing and its mechanism of color stabilization - Liuyao He; Wuyin Weng; Zhongyang Ren; Ping Li; Yucang Zhang; Linfan Shi (Food Chemistry, 2026)

Dual-functional nanotherapeutics: A novel approach to siRNA-mediated TNF-α silencing in inflammatory bowel disease - Li Qiao; Xue-Tian Qian; Yi-Gang Zhang; Xia-Feng Peng; Qi Liu; Shi-Qi Chang; Chang Cui; Feng Zhang; Shu-Kui Wang; Ning-Ping Huang (Chemical Engineering Journal, 2026)

Mechanistic insights into sucralose immunotoxicology: Dose-related modulation of the gut-immune axis in food allergy - Wenyan Li; Qiang Shi; Yifan Nie; Zhongliang Wang; Shuangyan Zheng; Ping Tong; Jinyan Gao; Yong Wu; Hongbing Chen (Chemico-Biological Interactions, 2026)

Multipathway Pesticide Exposure and Cross‐Scale Risk Assessment in Integrated Rice–Crab Aquaculture - Dan‐Dan Bian; Shi‐Rong Li; Bo‐Ping Tang; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
Integrated rice–crab co‐culture represents a sustainable agroecosystem, yet a critical conflict arises: pesticide applications necessary for rice cultivation undermine the health of the co‐cultured Chinese mitten crab ( Eriocheir sinensis ) and jeopardize system sustainability. To address this challenge, a comprehensive analytical framework is developed, linking multipathway pesticide exposure, molecular toxicity mechanisms, cross‐scale risk assessment, and resilience‐oriented governance. This framework systematically reviews the environmental fate and exposure dynamics of pesticides in paddy fields, as well as their toxicokinetics and tissue‐specific bioaccumulation in E. sinensis . Moving beyond descriptive toxicology, the study integrates “effect hierarchy” and “mechanistic network” perspectives to unravel cascading toxicity pathways, spanning oxidative stress, neuroendocrine disruption, cellular pyroptosis, and immune suppression. The limitations of conventional risk assessment in such a complex system are critically examined, with emphasis on the dual risks to crab population resilience and human food safety. To mitigate these challenges, a novel, mechanism‐informed “Prevent–Intercept–Protect–Adapt (PIPA)” framework is proposed to bolster system resilience, combining green pest control, eco‐engineering, host health enhancement, and smart monitoring. This review enhances theoretical understanding of contaminant impacts in multitrophic systems and offers actionable management strategies to promote the sustainable development of integrated aquaculture.

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Synergistic H2S production and CO2 capture from copper smelting neutralized gypsum slag: Process optimization, reaction mechanism and CaCO3 crystal regulation - Yuwen Deng; Jiyao Shi; Sisi Chen; Huidong Tang; Xiaofeng Huang; Xin Sun; Kai Li; Lei Shi; Ping Ning (Journal of Environmental Management, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Methane production in the stems of living trees in subtropical forests - Zhi-Ping Wang; Josep Barba; Jian-Guo Xue; Xiang-Cheng Mi; Ang Li; Zhen-Ying Huang; Shi-Jie Han (Planta, 2026)

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Taxadendins A-P, previously undescribed abietane diterpenoids with diverse structures from the bark of Taxodium ascendens - Zhi-Ping Zhou; Wen-Yan Li; Qin-Shi Zhao (Phytochemistry, 2026)

GEFmeso restricts JAK/STAT signaling to regulate border cell migration in Drosophila melanogaster - Liying Shi; Yuanyuan Song; Jiahang Li; Xiping Yu; Yanchao Wang; Ling Jiang; Enhui Shao; Ping Wan (Insect Biochemistry and Molecular Biology, 2026)

Multi-dimensional analysis revealing the mechanism of T-2 toxin driving liver fibrosis: integration of network toxicology, machine learning, experimental verification, and molecular docking - Lichun Qiao; Shaoteng Shi; Liangjia Wang; Muhammad Aftab Shafiq; Jing Tang; Miaoqian Li; Ping Wan; Jingxuan Zhou; Xulei Dai; Jing Han; Yijie Guo (Chemico-Biological Interactions, 2026)

Community traits and assembly mechanisms of comammox Nitrospira across maize, rice, and forest ecosystems in Eastern China - Xiang Li; Mingmei Lu; Yarui Shi; Tengyu Feng; Xiaoting Zheng; Ping Liu; Ruixian Yang; Kesheng Zhang; Xuesong Luo (Journal of Soils and Sediments, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Climate-smart straw return amplifies CO2 fertilization effects while decoupling N2O emissions: Evidence from soil metagenomics and metabolomics - Ruonan Duan; Wei Gao; Qiqi He; Zhichao Zhai; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Journal of Cleaner Production, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Corrigendum to “Quercetin attenuates cisplatin-induced mitochondrial apoptosis via PI3K/Akt mediated inhibition of oxidative stress in pericytes and improves the blood labyrinth barrier permeability” [Chemico-Biological Interactions 393 (2024) 110939] - Tian-lan Huang; Wen-jun Jiang; Zan Zhou; Tian-feng Shi; Miao Yu; Meng Yu; Jun-qiang Si; Yan-ping Wang; Li Li (Chemico-Biological Interactions, 2026)

Osteopontin-driven TGF-β1 signaling via integrin αvβ3-NF-κB axis impairs NK cell function in head and neck squamous cell carcinoma - Zhe Shen; Xin Li; Shi Luo; Yuzhang Gao; Imadoudini Hassimi Safia; Jie Jiang; Xin Qi; Wei Huang; Yalan Liu; Xing Fang; Yaoyun Tang; Ping Wu (Apoptosis, 2026)

Uncovering the Community Structure and Adaptive Characteristics of Soil Protists Across Natural, Semi‐Natural and Highly Degraded Habitats - Shi‐wei Feng; Xiaonan Wang; Ping Wen; Jing‐li Lu; Zhuo‐hui Wu; Xinzhu Yi; Wen‐sheng Shu; Jie‐Liang Liang; Pu Jia; Jin‐tian Li (Environmental Microbiology, 2026)
Protists are vital to soil ecological functions. However, their diversity and community patterns remain poorly characterised across habitats. This study investigated protists in 270 samples spanning five terrestrial ecosystems: natural (forest, grassland, desert), semi‐natural (farmland) and highly degraded (mine wasteland). The species richness of protists and the consumer functional group were highest in farmland and lowest in mine wasteland. We demonstrated that habitat type ( R partial Mantel = 0.291) exerted stronger effects on protistan communities than geographic distance ( R partial Mantel = 0.072). While α‐diversity drivers varied among habitats (e.g., total phosphorus (TP) was only positive in farmland and forest), β‐diversity was consistent and significantly correlated with mean annual temperature (MAT), mean annual precipitation (MAP), aridity index (AI) and moisture. We identified nine potential ecological groups of protists, reflecting their adaptive differentiation. To explore community assembly, a null model was conducted, revealing that stochastic processes dominated all habitats. Furthermore, co‐occurrence networks of protists, prokaryotes and fungi showed lower modularity and stability in mine wasteland compared with other habitats, indicating co‐occurrence patterns may be more specialised under resource limitation. Collectively, our results highlight the importance of habitat type in shaping protistan communities, suggesting that protists can be predictably regulated in degraded environments.

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Sequence Stratigraphy, Sedimentary Evolution and Controlling Factors of the Shan-1 Member in Permian Shanxi Formation, Qingyang Gas Field, Ordos Basin, Central China - Qian-qian Fan; Shi-qiang Xia; Hui Xia; Wei Wang; Long Wang; Yan Wang; Shi-cheng Wang; Shuai-shuai Feng; Wei Zhang; Ya Li; Ping Liu; Qian-yun Dong (Applied Geophysics, 2026)

Production of eggshell-polypyrrole composites for enhanced Cr (VI) removal from wastewater: Mechanisms and optimization - Jiayin Xie; Size Li; Xinru Yang; Xueming Qin; Ping Sun; Lve Shi; Hongmin Li; Yongsheng Zhao (Journal of Water Process Engineering, 2026)

Detecting drought propagation pathways in different climatic regions of China - Zhaoqiang Zhou; Linqi Li; Yibo Ding; Yiyang Zhao; Haiyun Shi; Renjie Hou; Ping Wang; Ping Xue; Tian Wang; Peng Chen (Journal of Hydrology, 2026)

Dual-metal sites synergy in Fe/V-N-C catalyst: Boosting ECL signals for ultrasensitive detection of aflatoxin B1 in corn and peanut - Ping Yuan; Ai-Jun Wang; Li-Ping Mei; Yacheng Shi; Pei-Xin Yuan; Jiu-Ju Feng (Food Chemistry, 2026)

Next-generation chitosan biodegradable films reinforced with bioactive acid-DES: A sustainable solution for improved mechanical, antibacterial, and anti-browning properties - Dehong Lu; Huimin Yao; Nouman Ali Shah; Sajid Ali; Li-Yan Zeng; Ping Shi; Yuan-Sen Liu; Ziru Dai; Hafiz Umer Javed (Carbohydrate Polymers, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Activating FcγRI inhibits RIG-I-mediated host antiviral innate immunity by FGR during PRRSV-ADE infection - Peng-li Xu; Yi-han Li; Fa-hao Li; Shi-jie Zhao; Wen Li; Jing Chen; Ping-an Xia; Yi-na Zhang (Veterinary Microbiology, 2026)

GmMYB84, a transcription factor, confers cadmium tolerance in soybean via regulation of the phenylpropanoid pathway - Zehua Gong; Jinni Zhao; Jing Xu; Zhichao Zhai; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Plant Science, 2026)

Distribution, fate, and risk prioritization of antibiotics in wastewater treatment plants in Northwest China: Insights into secondary sedimentation limitations and membrane process advantages - Yixi Zhang; Mengcheng Wu; Yunzhou Tan; Bo Du; Mengjiao Li; Liangliang Liu; Ping Wu; Guodong Kang; Shenghu Zhang; Zhengxiang Shi; Leilei Lu (Journal of Water Process Engineering, 2026)

An impact-based drought classification method using real-world agricultural drought records and explainable automated machine learning - Keke Zhou; Jianzhu Li; Ting Zhang; Xiaogang Shi; Ping Feng (Journal of Hydrology, 2026)

Partitioned N-TiO2–N-TiO2@SWCNT/PET composite fabric for industrial wastewater habitat reconstruction and potential cross-niche carbon sequestration - Jian Qiu; Yang Hu; Ying Chen; Shilong Li; Yudong Yuan; Bin Chen; Ping Shi; Jianfa Zhao; Wenheng Jing; Wei Zhou; Yuan Bai; Lele Cui; et al. (Journal of Environmental Chemical Engineering, 2026)

Seasonal dynamics of aqueous phase from hydrothermal carbonization of waste activated sludge: Unraveling composition, ecological risks, and resource opportunities - Tingting Yang; Ninghui Song; Xue Zhang; Yanqi Shi; Ping Li; Mingzhu Zhang; Feng Ge (Journal of Cleaner Production, 2026)

Persistent site-scale warming associated with solar photovoltaic installations - Chao Zhang; Wanjiao Li; Junjie Tang; Zhe Shi; Fanyu Suo; Shujie Zhang; Yulu Ke; Hongxing Hu; Ning Ai; Yong Gao; Ping Gong; Guo Yu Qiu (Journal of Environmental Management, 2026)

Investigation of pipe–soil interface effects on the stress–deformation behavior of buried high-density polyethylene pipes: full-scale test and analytical solution - Yuchen Zhang; Jianyong Shi; Yu Ping Li; Shi Shu; Xun Wu (Computers and Geotechnics, 2026)

Multiscale Fracture Evolution in Deep Hard Rock Masses Under Strong Excavation Disturbances: Stress-Mineral Synergy Unraveled Through Integrated 3D DEM–FDM Modeling and Borehole Monitoring - Xiu-Yang Liu; Ding-Ping Xu; Quan Jiang; Shao-Jun Li; Shi-Li Qiu; Yong Xia (Rock Mechanics and Rock Engineering, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

An Integrated U-Net and Markov Random Field Approach for Pavement Crack Segmentation - Shi-cai Yuan; Ding-zhi Liu; Wei-ping Shi; Pan Li; Yong-qiang Li; Yong Yi (Applied Geophysics, 2026)

New perspectives on key bioactive molecules of lactic acid bacteria: integrating targeted screening, key gene exploration and functional evaluation - Shi Hu; Qi Wang; Jinfeng Wu; Hangjia Zhang; Jiaqi Yin; Lina Ding; Ping Li; Hang Xiao; Qing Gu; Jiarun Han (Critical Reviews in Food Science and Nutrition, 2026)

Transcriptomic and physiological responses of Epinephelus akaara to chronic cold stress - Jichun Li; Huilai Shi; Suzhen Ran; Jianshe Zhang; Xiaolong Yin; Hongling Ping; Tao Zhang; Jiji Li; Bin Li; Yingying Ye (Aquaculture, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

Balancing grassland ecology and herders’ economic benefits: The impact of Grassland ecological compensation policy in Inner Mongolia - Chunjun Shi; Ping Li; Jingpeng Guo (Land Use Policy, 2026)

Performance assessment of an electrokinetic barrier-aquifer system using a dual-domain solute transport model - Jian-Ping Li; Zhang-Long Chen; Shi-Jin Feng; Wen Zheng; Gang Wang (Journal of Hydrology, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Unraveling the ranitidine removal mechanism in a novel riboflavin-mediated ultraviolet/peracetic acid system: An integrated density functional theory-machine learning framework - Yizhe Ding; Jiacheng Shi; Yuqian Lin; Qiya Sun; Yuxiang Zhao; Xi Wang; Qian Ping; Lin Wang; Yongmei Li (Journal of Hazardous Materials, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Hydrothermal stress influences the spatial distribution pattern of soil organic carbon and its stock in Xinjiang - Yunhao Li; Mingjie Shi; Ping'an Jiang; Jinzhi Gu; Jia Guo; Jiahao Zhao; Gongxin Wang; Yanmin Fan; Hongqi Wu (CATENA, 2026)

Metabolomic analysis of coloration mechanism of bamboo sheaths in different cultivars of Chimonobambusa utilis - Yan Lan; Xiao Zhu; Guang-Qian Gou; Ai-Juan Tan; Zhao-Xia Dai; Shi-Ping Huang; Gui-Li Yang (Physiology and Molecular Biology of Plants, 2026)

Drag reduction and shear stress saturation caused by tide-induced high suspended sediment concentration in the bottom boundary layer - Ya Ping Wang; Jin Li; Renzhi Li; Jingdong Chen; Yan Li; Yining Chen; Shu Gao; Aijun Wang; Benwei Shi; Jianhua Gao; Yang Yang (Geo-Marine Letters, 2026)

Long-term no-tillage altered microbial communities and reduced C degradation while facilitating denitrification in a semi-arid cropland - Yuzheng Zong; Weifeng Wang; Wanhong Jin; Yinglan Chen; Shaohui Jia; Qian Liu; Yali Cao; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Applied Soil Ecology, 2026)

Advanced technologies of artery-on-a-chip: a review of construction strategies and disease models - Shi-Qi Chang; Li Qiao; Oluwatosin David Abodunrin; Lin Zou; Ning-Ping Huang (Angiogenesis, 2026)

Palynological succession in Gzhelian No. 8 Thick Coal of the Taiyuan Formation, Ordos Basin, North China - Hui Zhang; Yun-He Shi; Peng-Shuai Jiao; Bo Pan; Feng Liu; Ming-Li Wan; Jing-Kun Zhang; Hui-Ping Peng (Palaeoworld, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

Breaking the HCl/SO2 selectivity barrier: Intrinsic basic properties of MDEA/SBA-15 for HCl removal - Xingguang Hao; Ying Zhu; Lei Shi; Fei Wang; Xin Sun; Ping Ning; Kai Li (Fuel, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Molecular Responses of Cold Stress Adaptation in the Red Grouper (Epinephelus Akaara): Compensatory Regulation Between FOXO and MAPK Signaling Pathways - Bin Li; Jichun Li; Hongling Ping; Tao Zhang; Jie He; Suzhen Ran; Jianshe Zhang; Xiaolong Yin; Yingying Ye; Huilai Shi; Jiji Li (Marine Biotechnology, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Molecular signature evolution of dissolved organic matter in wastewater during far-ultraviolet/peracetic acid disinfection: Integrated characterization and machine learning - Nuo Peng; Qiya Sun; Yuxiang Zhao; Yizhe Ding; Jiacheng Shi; Qian Ping; Lin Wang; Yongmei Li (Water Research, 2026)

The appearance of microblade technology at the onset of Marine Isotope Stage 2 in Northeast China - Wei Liu; Jian-Ping Yue; You-Qian Li; Ke-Liang Zhao; Si-Qi Lu; Guang-Yi Bai; Yang Liu; Yu-Xiu Zhang; Shi-Xia Yang (Quaternary Science Reviews, 2026)

Quantifying the climate mitigation potential of China's South-to-North Water Transfer Megaproject - Wenyang Shi; Zhongbin B. Li; Ping Lu; Zhenci Xu (Journal of Cleaner Production, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Mild magnetic hyperthermia-enhanced perfusion chemotherapy against bladder cancer - Han Jiang; Siqian Li; Hanyong Dong; Jing Wang; Ping Hu; Jianlin Shi (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Detecting and comparing extinction debts of amphibians in China under climate change - Yu-Xiao He; You-Hua Chen; Xiao-Qin Shi; Chao-Sheng Mu; Dan-Dan Yu; Jia-Qi Li; Hai-Gen Xu; Jian-Ping Jiang (Biological Conservation, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Aboveground living plant-based methane production does not dominate methane emissions in terrestrial ecosystems - Zhi-Ping Wang; Luke C. Jeffrey; Josep Barba; Katerina Machacova; Xi-Mei Zhang; Ang Li; Shi-Jie Han (Planta, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Ferroptosis at the intersection of radiotherapy and immunotherapy - Gui-Xia Wei; Ya-Qin Zhao; Rong Tang; Hua-Shan Shi; Zhi-Ping Li (Cancer and Metastasis Reviews, 2025)

Coupled biogeochemical processes account for vertical heterogeneity of groundwater iodine in the Hetao Basin - Junxia Li; Xingtao Liu; Zhou Jiang; Liang Shi; Yanhong Wang; Ping Li; Xianjun Xie; Yanxin Wang (Water Research, 2025)

Electrochemical energy storage systems: A review of types/functionalities, management systems and integration for real-life applications - Li-hua Ye; Josephine Baffoe; Eliasu Issaka; Yefan Shi; Hao Chen; Ai-ping Shi; Muhammad Muzamal Ashfaq (Next Research, 2025)

Contrasting influences of diurnal patterns and rainfall events on riverine CO2 degassing: insights from in situ high-resolution monitoring - Jianhong Li; Tao Zhang; Junbing Pu; Changchun Huang; Shi Yu; Kun Ren; Ping’an Sun; Qiong Xiao (Journal of Hydrology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Synergistic photothermal-magnetic nanoplatform: Recyclable TEG-SPIONs for ultra-efficient pathogen elimination in medical wastewater - Fei Ge; Yimei Wang; Jun Ge; Guoqiang Yang; Xinxin Liu; Shuxian Hou; Xuechao Shi; Yao Xiao; Shujie Li; Weiwei Zhang; Wanzhen Li; Ping Song; et al. (Journal of Environmental Chemical Engineering, 2025)

Impact of regionally transported biomass burning on carbonaceous aerosol characterization, contribution and degradation in Pu'er, Southwest China - Jianwu Shi; Wenjun Rao; Chenyang Zhao; Li Deng; Xinyu Han; Wei Du; Jianhong Huang; Senlin Tian; Ping Ning; Jiming Hao; Yaoqian Zhong (Journal of Environmental Sciences, 2025)

Development of eco-friendly chitosan films enhanced with bioactive citric acid-based deep eutectic agents for sustainable food packaging and fish preservation - Ping Shi; Xin Wang; Sajid Ali; Li-Yan Zeng; Xinhui Xian; Jinling Huang; Shengyun Qin; Yuansen Liu; Hafiz Umer Javed (Food Hydrocolloids, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Characterization of pivotal metabolites influencing the production of milk components in dairy goats - Mengke Ni; Xinran Luo; Yifan Li; Wenbo Zhang; Xiaochen Qin; Ping Wang; Huaiping Shi; Jun Luo; Cong Li (Food Chemistry, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

Analysis of the coupling between land use conflicts and ecosystem health in mountainous regions in China - Xiangyun Shi; Ping Ren; Li Peng; Wei Sun (Environment, Development and Sustainability, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Failure Mechanisms of Granite in Deep Underground Caverns Influenced by Rock Veins: Insights from DEM-FDM Cross-Scale Coupling and Moment Tensor Analysis - Xiu-Yang Liu; Ding-Ping Xu; Quan Jiang; Shao-Jun Li; Kang Bian; Shi-Li Qiu (Computers and Geotechnics, 2025)

High-entropy sulfide and nanozyme hybrid system with synergistic interface-engineering: Ultra-sensitive photoelectrochemical detection of chloramphenicol - Yi-Hong Chen; Ai-Jun Wang; Ya-Cheng Shi; Li-Ping Mei; Pei Song; Tiejun Zhao; Jiu- Ju Feng (Chemical Engineering Journal, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Fragments of ancient continental lithospheric mantle in the Mogok metamorphic Belt, Northern Myanmar: Re–Os isotope and platinum group element constraints - Qing-Hua Zhang; Bin Su; Yi Chen; Victoria Pease; Tou-Ping Peng; Zhu-Yin Chu; Yi-Bing Li; Kai-Hui Shi; Si Chen (Precambrian Research, 2025)

Identification and comparative genomic analysis of two Bacillus subtilis producing antifungal lipopeptide - Xue Bai; Lina Yi; Shuang Zhao; Jianlong Xiu; Ping Li; Rongjiu Shi; Xiaolong Liang; Ying Zhang (Pesticide Biochemistry and Physiology, 2025)

Field Tests Using High-Power Microwaves to Crack Iron Ore of Different Grades - Feng Lin; Xia-Ting Feng; Shi-Ping Li; Tian-Yang Tong; Yun-Tan Ao; Yu-Xi Liu (Rock Mechanics and Rock Engineering, 2025)

Isoliquiritigenin alleviates radiation-induced intestinal injury in lung cancer by inhibiting TNF-α/caspase3 signaling pathway - Ya-ping Chen; Liang-liang Shi; Yang-yang Li; Yi-Ming Zhang; Shang-zu Zhang; Hong-dou Hou; Yan Chen; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of dihydroagarofuran sesquiterpene from the fruits of Tripterygium hypoglaucum and evaluation of their anti-inflammatory activity - Shi-Li Wu; Xing Yang; Wen-Xiu Ning; Gang-Yun Wu; Xin-Yu Dai; Yu Zhang; Duo-Zhi Chen; Xiao Ding; Hong-Ping He; Wei Zhou; Xiao-Jiang Hao (Phytochemistry, 2025)

Association of microplastics in human cerebrospinal fluid with Alzheimer’s disease-related changes - Ping He; Feng Wang; Guangjun Xi; Yang Li; Fengyun Wang; Hui Wang; Lei Li; Xuemei Ma; Yan Han; Yachen Shi (Journal of Hazardous Materials, 2025)

Production regularity of exosomes and the characteristics of miRNA in exosomes from Eriobotrya Japonica L. suspension cells - Hui-hua Li; Mei-fang Wu; Qiu-ping Ye; Fei Chen; Wei Wang; Jian-yu Shi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

A Novel Selenite-Reducing Bacterium Bacillus pseudomycoides SA14 Isolated from Se-Enriched Soil and Its Potential Se Biofortification on Brassica chinensis L. - Xianxin Huang; Yanhong Wang; Helin Wang; Xinyan Shi; Chunlei Huang; Hanqin Yin; Yixian Shao; Ping Li (Journal of Earth Science, 2025)

Integrating ecological niche and epidemiological models to predict wheat fusarium head blight using remote sensing and meteorological data - Shangzhou Li; Ping Dong; Hui Zhang; Xin Xu; Lei Shi; Tong Sun; Hongbo Qiao; Jibo Yue; Wei Guo (Computers and Electronics in Agriculture, 2025)

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

Advances and challenges of medicine and food homology earthworms: active ingredients, efficacy and quality control - Siqi Lu; Xiaoqin Xie; Tao Xu; Junqi Dong; Shengrong Li; Zenghui Lu; Ping Shi; Pixian Gong; Wei Liu (Trends in Food Science & Technology, 2025)

Arsenic mobilization by Bathyarchaeia in subsurface sediments at the Jianghan Plain, China - Zhou Jiang; Wenjie Fang; Yongguang Jiang; Yidan Hu; Yiran Dong; Ping Li; Liang Shi (Journal of Hazardous Materials, 2025)

Study on the high-efficiency CO2 mineralization reaction mechanism of thermally modified materials from neutralized gypsum residue driven by sulfur vacancies in an aqueous environment - Yuwen Deng; Sisi Chen; Huidong Tang; Fei Wang; Yixing Ma; Lei Shi; Fan Du; Xin Sun; Kai Li; Ping Ning (Chemical Engineering Journal, 2025)

GWAS and GS analysis revealed the selection and prediction efficiency for yield, plant morphological, and fiber quality in Gossypium barbadense - Tao Yang; Honggang Wang; Jikun Song; Kang Zhao; Bo Pang; Yongpan Wang; Ping Luo; Weiwei Liang; Shunyu Shi; Jie Wang; Yifeng Lin; Jing Li; et al. (Theoretical and Applied Genetics, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Investigating the Potential Therapeutic Targeting of the JAK-STAT Pathway in Cerebrovascular Diseases: Opportunities and Challenges - Jia-Wei Wu; Bing-Xin Wang; Li-Ping Shen; Yong-Lin Chen; Zhi-Yong Du; Shi-Qing Du; Xiao-Jie Lu; Xu-Dong Zhao (Molecular Neurobiology, 2025)

Bioinspired copper-doped covalent organic polymers with laccase-mimicking activity for on-site monitoring of thiram in fruit and vegetable samples - Ya Di Shi; Meng Ping Wang; Han Wu; Sai Jin Xiao; Zi Yang Yue; Ding Zhong Yuan; Xin Xin Shao; Feng Tao Yu; Li Zhang (Analytica Chimica Acta, 2025)

Effects of Microclimates on Species Richness of Epiphytic and Non‐Epiphytic Bryophytes Along a Subtropical Elevational Gradient in China - Zun Dai; Hong‐Wei Zhang; Hong Qian; Min Li; Rui‐Ping Shi; Zhao‐Chen Zhang; Jian Zhang; Hong‐Qing Li; Jian Wang (Journal of Biogeography, 2025)
Aim Biodiversity patterns along elevational gradients have been well documented for vascular plants and terrestrial vertebrates, but we know relatively little about the elevational patterns of bryophytes and their underlying mechanisms, especially the effect of forest microclimate on epiphytic and non‐epiphytic bryophytes. Here we study the influence of microclimates on the richness of epiphytic and non‐epiphytic bryophytes as a whole, and for liverworts and mosses separately, in forests along an elevational gradient ranging from 369 to 1476 m in a subtropical region. Location Mt. Tianmu in eastern China. Methods We sampled bryophytes in each of 16 vegetation plots, each of the size of 20 by 20 m, along the elevational gradient and distinguished between mosses and liverworts and between epiphytic and non‐epiphytic species. We measured climate conditions at local sites. Species richness of bryophytes along the elevational gradient was related to six microclimate variables, using correlation and regression analyses and a variation partitioning approach. Results Overall, species richness of bryophytes showed a slightly decreasing trend with elevation, and epiphytic and non‐epiphytic bryophyte richness showed different elevational patterns. Compared to non‐epiphytic bryophytes, species richness of epiphytic bryophytes was more influenced by air microclimate. We also found that species richness of bryophytes was influenced by both microclimate extreme variables and microclimate seasonality variables. In sum, utilising in situ air and soil microclimatic monitoring data, our study offers a more accurate assessment of the relationship between bryophyte species richness and their habitats. Main Conclusions Our results highlight the importance of considering the ecological differences between mosses and liverworts, and distinguishing between microhabitats of sampled bryophyte assemblages when exploring the patterns and drivers of bryophyte diversity along elevational gradients.

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Performance of ethanol transformable microemulsions and remediation of salinized oil – contaminated soils - Xiaoning Feng; Nan Shi; Shuhai Guo; Bo Wu; Gang Li; Bin Lou; Xiujie Yang; Yifan Wang; Ping Xiang; Xiahong He; Dong Liu (Journal of Hazardous Materials, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Ethanol aqueous solution annealing improves the deodorization effects of V-type granular starch on oyster peptides - Peichao Chen; Wuyin Weng; Zhongyang Ren; Ping Li; Linfan Shi (Food Hydrocolloids, 2025)

Flexural behaviors of GFRP-reinforced Engineered Cementitious Composite (ECC)-concrete composite beams - Li-Hui Wang; Wen-Hao Shi; Lan-Ping Qian; Yu-Lei Bai; Shi-Zhu Liu; Zhan-Qun Yang (Engineering Structures, 2025)

Nitrification inhibitor shifts the composition of soil microbial communities and increases N utilization potentials in wheat soil under elevated CO2 concentration - Jing Yang; Xiaxuan Lai; Yan Wang; Lifeng Guo; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Plant and Soil, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Overexpression of Cucurbita pepo CpVQ27 increased susceptibility of tobacco to powdery mildew - Shi-heng Li; Ping Wang (Physiological and Molecular Plant Pathology, 2025)

Corrigendum to “Overexpression of pumpkin CpVQ30 increased susceptibility of tobacco to powdery mildew” [Volume 133, September 2024, 102365] - Shi-heng Li; Ping Wang (Physiological and Molecular Plant Pathology, 2025)

Effect of Cu/HZSM-5 sorbents with different Si/Al ratios on the adsorption and oxidation performance of H2S - Kaini Ma; Kai Li; Ping Ning; Jiayu Feng; Jiacheng Bao; Lei Shi; Xiangyu Wang; Xin Sun (Journal of Environmental Sciences, 2025)

Comparative analysis of volatile compounds of an oyster enzymatic hydrolysate adsorbed by V-type starches based on electronic nose, GC-IMS, and GC-MS - Peichao Chen; Yaolin Dai; Wuyin Weng; Zhongyang Ren; Ping Li; Linfan Shi (Food Research International, 2025)

Study on multi-objective joint optimization of water and sediment operation considering multiple uncertainties: a case study in the lower yellow river - Fangzheng Zhao; Peng Yi; Ping-an Zhong; Xinyu Wan; Jieyu Li; Sen Wang; Weiyi Shi; Xinyu Wang; Ke Zheng (Stochastic Environmental Research and Risk Assessment, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Impacts of Naphthenic Acids (NAs) Exposure on Soil Bacterial Community and Antibiotic Resistance Genes (ARGs) Dissemination - Qianzhi Zeng; Qiangwei Liu; Yunhong Pu; Ping Gong; Yuxin Li; Yanan Sun; Yiming Hao; Qing Yang; Yaxuan Wu; Bowen Yang; Shengnan Shi; Zheng Gong (Current Microbiology, 2025)

Penicipyrrolidines A−N, pyrrolidine derivatives with inhibitory effects on EMT and fibroblast activation from the mangrove-derived fungus Penicillium sp. DM27 - Li-Ming He; Xuan Deng; Li-Hua Ni; Shi-Qi Cai; Jinhu Chen; Zejin Liao; Mengke Zhang; Hua Shui; Kong-Kai Zhu; Song Wu; Ping Gao; Ariel M. Sarotti; et al. (Marine Life Science & Technology, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Metallization-mediated charge transfer in cocrystals for efficient photocatalytic decontamination of mustard-gas simulant - Li Zhang; Xiao-Lin Liu; Chen Sun; Yu-Ting Luo; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2025)

Effect of γ-Aminobutyric acid and dietary monosodium glutamate supplementation on gut microbiota and short-chain fatty acid: Insights from an in vitro colonic fermentation model - Jiarun Han; Xilian Zhao; Qiuqiu Ye; Yueting Wang; Yutong Wu; Shi Hu; Ping Li; Qing Gu (Food Bioscience, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

The complexities of cell death mechanisms: a new perspective in systemic sclerosis therapy - Xue Xia; Chenfei Kong; Xiaoming Zhao; Kelin Zhao; Naixu Shi; Jinlan Jiang; Ping Li (Apoptosis, 2025)

Pumpkin (Cucurbita pepo L.) CpVQ20 increases resistance to powdery mildew of tobacco through flavonoid and lignin biosynthesis pathways - Shi-heng Li; Ping Wang (Physiological and Molecular Plant Pathology, 2025)

Reconstruction of significant wave height for bottom-mounted acoustic profilers with pressure sensor failure: A case study - Junmin Li; Yifeng Tong; Yajun Xu; Wuyang Chen; Ping Shi (Ocean Engineering, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Long-term no tillage straw mulching increased soil water and nitrogen storage in dryland wheat on the Loess Plateau, but may increase dissolved organic nitrogen leaching - Xinrui Shi; Xiaowen Liu; Jianyun Jing; Yan Zhang; Ping Li; Yuzheng Zong; Dongsheng Zhang; Xingyu Hao (Field Crops Research, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The catalytic mechanism of cobalt-based sites in the oxidation of MgSO3 - Zhaorui Li; Xin Tang; Fei Wang; Kai Li; Shi Lei; Ning Ping; XingYi Ma; Xin Sun (Process Safety and Environmental Protection, 2025)

Identification of the Shuanglongtan tectonic mélange (ca. 1.7–1.5 Ga) in the southwestern Yangtze Block and it’s tectonic implications - Jun-Ping Liu; Zai-Bo Sun; Xiao-Hu He; Jiang-Tai Zhao; Shi-Jun He; Ling-Jing Bi; Wei-Ke Li (Precambrian Research, 2025)

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

Sulfadiazine degradation by Acinetobacter sp. strain H-3 and its applicability in soil at low temperatures - Shuang Zhao; Yi Zhang; Rongjiu Shi; Xiaolong Liang; Ping Li; Xue Bai; Siqin Han; Ying Zhang (International Biodeterioration & Biodegradation, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Anti-inflammatory oxazole-, nitro- and hexahydropyrrolo[2,1-b]oxazole-containing abietane diterpenoid alkaloids from Salvia miltiorrhiza - Li-Xia Wang; Shao-Jie Shi; Li-Ping Long; Xiao-Ping He; Peng Zhang; Xiao-Wen Yang; Yan Liu; Xue-Mei Niu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Huanglian decoction prevents and treats radiation-induced intestinal injury in lung cancer by regulating endoplasmic reticulum stress - Liang-liang Shi; Ya-ping Chen; Hao-ming Guo; Xue-peng Wang; Yang-yang Li; Shuai-zhe Wang; Shang-zu Zhang; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Journal of Natural Medicines, 2025)

Influence of Syncline Structures on Deformation and Failure in Anti-Dip Soft–Hard Rock Slopes - Chunhong Zhou; Lei Wang; Ping Wang; Wanli Liu; Yuchuan Shi; Feng Ji; Zhuo Li; Juncheng Wang (Geotechnical and Geological Engineering, 2025)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

The influence of steep faults at various avoidance distances on the stability of hard rock caverns: Physical model experiments and DEM simulations - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Shi-jie Chen; Guang-liang Feng; Quan Jiang; Xin-hao Zhu; Shu-qian Duan (Tunnelling and Underground Space Technology, 2024)

Recent development on drought propagation: A comprehensive review - Zhaoqiang Zhou; Ping Wang; Linqi Li; Qiang Fu; Yibo Ding; Peng Chen; Ping Xue; Tian Wang; Haiyun Shi (Journal of Hydrology, 2024)

Corrigendum to “An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community” [Food Res. Int. 196 (2024) 115052] - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

V-type starches for trimethylamine of sea cucumber intestinal peptides: Adsorption kinetics and mechanism - Shiqin Qing; Zhaoqing Yang; Wuyin Weng; Ping Li; Zhongyang Ren; Linfan Shi (Food Bioscience, 2024)

Effects of biochar and compost on the abundant and rare microbial communities assembly and multifunctionality in pesticide-contaminated soil under freeze‒thaw cycles - Guoxin Shi; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Qingshan Chen; Ping Xue (Environmental Pollution, 2024)

Chemical characteristics, sources, and formation mechanisms of PM2.5 before, during, and after the Spring Festival in a plateau city of Southwest China - Jianwu Shi; Li Deng; Wei Du; Xinyu Han; Yaoqian Zhong; Wenjun Rao; Haitao Xie; Feng Xiang; Ping Ning; Senlin Tian (Atmospheric Environment, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Foliar Application of Abscisic Acid Alleviates Cadmium Stress by Modulating Differential Physiological and Transcriptome Response in Leaves, Stems, and Roots of Mung Bean Seedlings - Yan Leng; Ping-Min Wu; Shi-Weng Li; Xiao-Jun Zhang (Journal of Plant Growth Regulation, 2024)

Effects of biochar on the transformation and utilization of nitrogen fertilizer in the black soil region of Northeast China - Guoxin Shi; Renjie Hou; Tianxiao Li; Qiang Fu; Qingshan Chen; Ping Xue; Xuechen Yang (Science of The Total Environment, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Physical and mechanical characterization of solid waste collected from rural areas of China: Experimental study - Yu-Ping Li; Baoyun Fan; Le Cheng; Jianyong Shi; Xiulei Li; Lianghu Su; Zeeshan Khursheed (Process Safety and Environmental Protection, 2024)

An isolated salt-tolerant Tetragenococcus halophilus 2MH-3 improved the volatile flavor of low-salt fermented fish sauce by regulating the microbial community - Jiarun Han; Shi Hu; Xin Zhao; Jialan Jiang; Qi Wang; Jinfeng Wu; Xilian Zhao; Ping Li; Qing Gu (Food Research International, 2024)

Atomic modulation of FeN4 sites on hollow carbon nanospheres by neighboring Mn atoms for ultra-stable Zn-air batteries - Zhaowei Ji; Chenglong Qiu; Ping Li; Yifan Li; Jing Shi; Jingyi Wu; Yue Zhu; Wei Hu; Zhi Li; Huanlei Wang (Chemical Engineering Journal, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Comparative mitogenomes of Lobotiformes provides insights into the phylogentic position of Hapalogenyidae - Li Gong; Kaixin Wang; Zhenming Lü; Liqin Liu; Tao Zhang; Hongling Ping; Huilai Shi (Regional Studies in Marine Science, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Investigating the thermal stability and calcium resistance of O/W emulsions prepared with glycosylated whey protein hydrolysates modified by different saccharides - Congzhen Shi; Yuanyuan Deng; Zhiming Wang; Yan Zhang; Xiaojun Tang; Zhihao Zhao; Ping Li; Pengfei Zhou; Guang Liu; Mingwei Zhang (Food Chemistry, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Overexpression of pumpkin CpVQ30 increased susceptibility of tobacco to powdery mildew - Shi-heng Li; Ping Wang (Physiological and Molecular Plant Pathology, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Sediment dynamic on the tidal flat sheltered by artificial engineering: A case study on eddies - Shaoxin Chen; Haifei Yang; Mingliang Li; Fei Xing; Benwei Shi; Ya Ping Wang (Estuarine, Coastal and Shelf Science, 2024)

Sulfadiazine degradation by Bjerkandera adusta DH0817 at low temperatures and its cold-adaptation mechanisms - Shuang Zhao; Rongjiu Shi; Xiaolong Liang; Ping Li; Xue Bai; Yongfeng Wang; Ying Zhang (Bioresource Technology, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Predicting the potential deterioration of Barrett’s esophagus based on gut microbiota: a Mendelian randomization analysis - Conghan Li; Panyin Shu; Taiyu Shi; Yuerong Chen; Ping Mei; Yizhong Zhang; Yan Wang; Xinyan Du; Jianning Wang; Yixin Zhang; Bin Liu; Zhijin Sheng; et al. (Mammalian Genome, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Effects of the nitrification inhibitor nitrapyrin on N2O emissions under elevated CO2 and rising temperature in a wheat cropping system - Yuzheng Zong; Na Qiu; Lujie Li; Yan Zhang; Xinrui Shi; Dongsheng Zhang; Xingyu Hao; Ping Li; Shu Kee Lam (Applied Soil Ecology, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Integrated analysis of the gonadal methylome and transcriptome provides new insights into the expression regulation of sex determination and differentiation genes in spotted scat (Scatophagus argus) - Kai-Zhi Jiao; Yu Li; Yuan-Qing Huang; Charles Brighton Ndandala; Gang Shi; Si-Ping Deng; Hong-Juan Shi; Hua-Pu Chen; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Strengthened oil-water separation by swirl vane hydrocyclone based on short-circuit flow regulation - Wei Zhao; Jian-ping Li; Tong Zhang; Aosong Wei; Shi-yun Li; Zi-heng Zhao; Xue-jing Yang; Xia Jiang; Hua-lin Wang (Journal of Water Process Engineering, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

Multiple stresses induced by chronic exposure to flupyradifurone affect honey bee physiological states - Jin Chen; Yong-Jun Liu; Qiang Wang; Li Zhang; Sa Yang; Wang-Jiang Feng; Min Shi; Jing Gao; Ping-Li Dai; Yan-Yan Wu (Science of The Total Environment, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

A versatile food packaging film fabricated by gallic acid/octanoic acid grafted chitosan: Preparation, characterization, high-efficient cells capture and photodynamic eradication of bacteria and biofilms - Ke Zhang; Lai Jiang; Ru-Kang Chen; Yu Shi; Yu-Gang Shi; Yue-Wen Chen; Rammile Ettelaie; Ping Li (Food Hydrocolloids, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

Estimating the Mechanical Properties of Rocks and Rock Masses Based on Mineral Micromechanics Testing - Xiu-yang Liu; Ding-ping Xu; Shao-jun Li; Shu-qian Duan; Huai-sheng Xu; Quan Jiang; Shi-li Qiu (Rock Mechanics and Rock Engineering, 2024)

α-Fe2O3 nanorods on CoFe-LDH@MX via interfacial interactions for Congo red removal: Experimental and mechanistic studies - Xianyong Hong; Mingxing Shi; Linrui Li; Zhoutian Ding; Zhiren Zhao; Ping Du; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Bacterial structures and their associated ARGs in Shanghai subway air, China - Lijun Zhang; Xiaojing Li; Yongping Liu; Yi Zheng; Lisha Shi; Yichen Ding; Jian Chen; Ping Xiao (Journal of Aerosol Science, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Edible composite films: enhancing the postharvest preservation of blueberry - Dongfang Shi; Boya Zhao; Pingping Zhang; Ping Li; Xinpei Wei; Kai Song (Horticulture, Environment, and Biotechnology, 2024)

Karyotype analysis of Chinese chive germplasms with different ploidy levels and their evolutionary relationships - Peng-Qiang Yao; Jian-Hua Chen; Pei-Fang Ma; Li-Hua Xie; Jiang Shi; Shi-Ping Cheng (Genetic Resources and Crop Evolution, 2024)

The effect of elevation, latitude, and plant richness on robustness of pollination networks at a global scale - Xiang-Ping Wang; Jeff Ollerton; Kit S. Prendergast; Jin-Chao Cai; Ma-Yin Tong; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Arthropod-Plant Interactions, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Bio-sorption capacity of cadmium and zinc by Pseudomonas monteilii with heavy-metal resistance isolated from the compost of pig manure - Ping Wang; Feixue Yue; Cong Shao; Qian Li; Yining Shen; Kaili Xu; Zihan Shi; Naiyu Liu; Ronghua Li; Zengqiang Zhang (Bioresource Technology, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Effect of Perilla seeds inclusion on the performance, egg quality characteristics, biochemical parameters and egg yolk fatty acid composition of laying hens - Ping Li; Samiullah Khan; Yanhua Huang; Shengtao Lu; Panhong Zhou; Jiale Ling; Tianzheng Xu; Xiaoli Shi (Tropical Animal Health and Production, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Bakuchiol regulates TLR4/MyD88/NF-κB and Keap1/Nrf2/HO-1 pathways to protect against LPS-induced acute lung injury in vitro and in vivo - Li Zhao; Zhengliang Zhang; Ping Li; Yanxia Gao; Yu Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Sesquiterpenes from Inula macrophylla and their anti-neuroinflammatory activity - Rui Ma; Bakhrom Komilov; Cheng-Bo Wang; Komila Alibekovna Eshbakova; Jun-Li Yang; Wei Ha; Yan-Ping Shi (Phytochemistry Letters, 2024)

Electrokinetic bioremediation of trichloroethylene and Cr/As co-contaminated soils with elevated sulfate - Qizheng Cai; Chongwen Shi; Zixuan Cao; Zhengtao Li; He-Ping Zhao; Songhu Yuan (Journal of Hazardous Materials, 2024)

The removal mechanisms of HF and HCl gases using Mg-Al adsorbent prepared by sol-gel synthesis method - Peng Gao; Jiayu Feng; Yuxuan Xie; Xinyu Yang; Ping Ning; Xin Sun; Fei Wang; Lei Shi; Jie Zhao; Kai Li (Journal of Environmental Chemical Engineering, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Windows of sensitivity for risk of adverse birth outcomes related to gestational PM2.5 exposure: Evidence from a natural experiment - Wei Ni; Yuhan Xing; Guoju Li; Zhanhui Du; Ping Yang; Qinzheng Wang; Xinmeng Yang; Bei Lyu; Hongge Fa; Qiuling Shi; Quansheng Xing (Environmental Pollution, 2024)

Quercetin attenuates cisplatin-induced mitochondrial apoptosis via PI3K/Akt mediated inhibition of oxidative stress in pericytes and improves the blood labyrinth barrier permeability - Tian-Lan Huang; Wen-Jun Jiang; Zan Zhou; Tian-Feng Shi; Miao Yu; Meng Yu; Jun-Qiang Si; Yan-Ping Wang; Li Li (Chemico-Biological Interactions, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Enhanced absorption of SO2 from phosphogypsum decomposition by phosphate slurry for phosphoric acid production - Wenmin Qian; Yanyu Yang; Zewei Liu; Jin Zhang; Xin Song; Nan Shi; Ming Xie; Bin Li; Ping Ning (Journal of Hazardous Materials, 2024)

Effects of hydrogen peroxide on the combustion and emissions of an ethanol/gasoline combined injection engine under different excess air ratios - Jufang Zhang; Ping Sun; Weibo Shi; Xiumin Yu; Decheng Li; Yinan Li; Tianqi Wang; Zhe Zhao; Tianyang Gong (Fuel, 2024)

Deep plowing increases soil water storage and wheat yield in a semiarid region of Loess Plateau in China: A simulation study - Xinrui Shi; Chao Li; Ping Li; Yuzheng Zong; Dongsheng Zhang; Zhiqiang Gao; Xingyu Hao; Jing Wang; Shu Kee Lam (Field Crops Research, 2024)

Combined inhibitory effects of microcystin-LR and microcystin-RR on growth and development in zebrafish larvae - Xiao-chun Guo; Shao-yong Lu; Sheng-nan Zhang; Ping Xie; Guang-yu Li; Zu-qin Shi; Yi-tong Zhou; Yu-meng Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Sustainable management and valorization of biomass wastes using synthetic microbial consortia - Shi-Peng Zhou; Xia Ke; Li-Qun Jin; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2024)

Emissions of polycyclic aromatic hydrocarbons in PM2.5 emitted from motor vehicles exhaust (PAHs-PM2.5-MVE) under the plateau with low oxygen content - Qinzuo Yao; Jianwu Shi; Xinyu Han; Senlin Tian; Jianhong Huang; Yingjie Li; Ping Ning (Atmospheric Environment, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

Quercetin stimulates an accelerated burst of oviposition-based reproductive strategy in codling moth controlled by juvenile hormone signaling pathway - Bing Bai; Shi-Pan Zhang; Yu-Ting Li; Ping Gao; Xue-Qing Yang (Science of The Total Environment, 2024)

Metabolomics analysis to interpret changes in physiological and metabolic responses to chronic heat stress in Pekin ducks - Xiangyi-Yi Zeng; Arshad Javid; Gang Tian; Ke-Ying Zhang; Shi-Ping Bai; Xue-Mei Ding; Jian-Ping Wang; Li Lv; Yue Xuan; Shan-Shan Li; Qiu-Feng Zeng (Science of The Total Environment, 2024)

Evaluations of extreme wave heights around Hainan Island and their uncertainty induced by decadal variations of input variables - Junmin Li; Shaotian Li; Yineng Li; Wuyang Chen; Bo Li; Junliang Liu; Ping Shi (Ocean Engineering, 2024)

Factors controlling the heavy metal ion activity in soil contaminated by microplastics with different mulch durations: Partial least squares path model - Huarong Sun; Yilan Shi; Chaohang Li; Siran He; Yinghao Bai; Ping Zhao; Dan Qiu; Jiamin Liu; Shuran He (Journal of Hazardous Materials, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Selective adsorption of volatile compounds of oyster peptides by V-type starch for effective deodorization - Yaolin Dai; Zhongyang Ren; Ping Li; Yucang Zhang; Wuyin Weng; Linfan Shi (Food Hydrocolloids, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Define of Optimal Addition Period of Osteogenic Peptide to Accelerate the Osteogenic Differentiation of Human Pluripotent Stem Cells - Yameng Song; Hongjiao Li; Zixuan Wang; Jiamin Shi; Jing Li; Lu Wang; Lingzi Liao; Shengqin Ma; Yun Zhang; Bin Liu; Yaling Yang; Ping Zhou (Tissue Engineering and Regenerative Medicine, 2024)

Integration of transcriptome and metabolome reveals the accumulation of related metabolites and gene regulation networks during quinoa seed development - Qianchao Wang; Jirong Shi; Junna Liu; Ping Zhang; Li Li; Heng Xie; Hanxue Li; Hongxin Wang; Chenghong Liu; Peng Qin (Plant Molecular Biology, 2024)

Expansion of YALIcloneHR toolkit for Yarrowia lipolytica combined with Golden Gate and CRISPR technology - Qi Shen; Fang Yan; Ya-Wen Li; Jian Wang; Jia Ji; Wen-Xin Yan; Dan-Chen He; Ping Song; Tian-Qiong Shi (Biotechnology Letters, 2024)

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Particulate polycyclic aromatic hydrocarbons in rural households burning solid fuels in Xuanwei County, Southwest China: occurrence, size distribution, and health risks - Xinyu Han; Dingshuang Li; Wei Du; Jianwu Shi; Shuai Li; Yuqi Xie; Shihan Deng; Zhihao Wang; Senlin Tian; Ping Ning (Environmental Science and Pollution Research, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Environmentally persistent free radicals on photoaged nanopolystyrene induce neurotoxicity by affecting dopamine, glutamate, serotonin and GABA in Caenorhabditis elegans - Hui Li; Yulun Gu; Yongqi Jiang; Ping Ding; Xiaoxia Chen; Chao Chen; Ruolin Pan; Chongli Shi; Susu Wang; Haibo Chen (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Gas barrier coating based on cellulose nanocrystals and its preservation effects on mango - Mingxia Li; Zhenxu Shi; Shulin He; Qiang Hu; Ping Cai; Lin Gan; Jin Huang; Yongqiang Zhang (Carbohydrate Polymers, 2023)

A Case of Kerion Complicating with Acute Generalized Exanthematous Pustular Dermatophytid (AGEPD) - Li Tang; Hongjian Shi; Ping Zhan; Zhihua Li; Qing Jiang; Xiaobing Wang; Weijun Liu (Mycopathologia, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Variability of Arctic Sea ice age and its relationship with atmospheric circulation patterns - Ping Chen; Xiaoyu Wang; Jinping Zhao; Tao Li; Junqiang Shi; Fangyi Zong; Lai Wei (Frontiers in Marine Science, 2023)
Since at least the 1990s, global warming has caused the decline of multi-year ice (MYI) in the Arctic, which has made the Arctic Ocean more susceptible to the effects of climate change and weather processes. In this study, an analysis of the variations in Arctic sea ice age was carried out based on the results of an Empirical Orthogonal Function (EOF) analysis. Variations in three time periods were investigated. The first period (1984-1995) is characterized by high sea ice age, with antiphase variation processes in the eastern and western parts of the Arctic Ocean. The second period (1996-2012) represents a rapid reduction in ice age, characterized by a gradual replacement of MYI in the Arctic Ocean with seasonal sea ice, resulting in a decreased extent of MYI. The third period (2013-2022) is characterized by low sea ice age, with ice age being in a significantly negative phase. Furthermore, trend-like changes were weak during this period. During the first period, the spatial distribution and significant variations in ice age were driven by cyclonic wind anomalies associated with the Arctic Oscillation (AO) atmospheric pressure modes. The cyclonic wind fields in winter and anticyclonic wind fields in summer collectively influenced the sea ice. This led to a decrease/increase in ice age in the eastern/western Arctic, and antiphase variations were apparent. During the second study period, winter ice age variations were driven by cyclonic wind anomalies associated with the AO atmospheric pressure modes, leading to ice divergence and a decrease in ice age. In summer, both thermodynamic (Arctic warming) and dynamic (DA) mechanisms play a role in modulating the changes of sea ice age, while Arctic warming is the primary driver. The DA generated anomalous wind patterns, characterized by the Beaufort Gyre and Transpolar Drift, which resulted in the outflow of MYI from the Arctic under the influence of meridional winds. During the third study period, the influence of AO/DA and air temperature on sea ice age changes is greatly weakened.

Electrical stimulation induces anti-tumor immunomodulation via a flexible microneedle-array-integrated interdigital electrode - Yixuan Pan; Yangxi Zhang; Xueying Shi; Dongdong Li; Xiaodan Xu; Bing Xiao; Ying Piao; Jiajia Xiang; Shiqun Shao; Frederic Chun-Yip Ho; Youqing Shen; A. Ping Zhang; et al. (Science Bulletin, 2023)

Experimental study of load characteristics caused by underwater explosion bubble collapsing in the neighborhood of a rigid wall - Qi Wang; Lin-Han Feng; Nian-Nian Liu; Mao Li; Peng-Duo Zhao; Lei Zhang; Shi-Ping Wang (Ocean Engineering, 2023)

Repair of dysfunctional bone marrow endothelial cells alleviates aplastic anemia - Shu-Qian Tang; Tong Xing; Zhong-Shi Lyu; Li-Ping Guo; Mi Liang; Chen-Yuan Li; Yuan-Yuan Zhang; Yu Wang; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

Transcriptome Analysis Revealed the Differential Molecular Response Mechanisms of Roots, Stems, and Leaves in Mung Bean to Cadmium Stress - Ping-min Wu; Yan Leng; Shi-Weng Li; Yu-Lin Wang; Fu-Jun Qiao (Journal of Plant Growth Regulation, 2023)

Invasive Asteraceae plants can enhance community stability by changing pollination network structure, yet cause intense pollen disturbance to native plants in an oceanic island community - Xiang-Ping Wang; Xiao Fu; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Biological Invasions, 2023)

Clerodane diterpenoids from the Uygur medicine Salvia deserta with immunosuppressive activity - Xue Ren; Xin Yuan; Shan-Shan Jiao; Xiao-Ping He; Hong Hu; Juan-Juan Kang; Shi-Hong Luo; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2023)

New nornemoralisin and nemoralisin diterpenoids from Aphanamixis polystachya - Yan-Wu Chen; Shi-Li Wu; Fa-Wu Dong; Hua-Yi Jiang; Hong-Ping He (Phytochemistry Letters, 2023)

A neglected contributor of thermal hydrolysis to sludge anaerobic digestion: Fulvic acids release and their influences - Mingze Shi; Hongbo Liu; Xuedong Zhang; Yajie Li; Fang Huang; Cheng Zhao; Jun Guo; Ping Wu; He Liu (Journal of Environmental Management, 2023)

Theoretical study of H-abstraction reactions of di-n-propyl ether oxidation by H, CH3, HO2 and OH radicals - Mengjiao Gao; Jiuning He; Shunping Shi; Xuefeng Liu; Yanhao Duan; Lei Chen; Changhua Zhang; Ping Li; Deliang Chen (Fuel, 2023)

Corrigendum to ‘Maltol attenuates polystyrene nanoplastic-induced enterotoxicity by promoting AMPK/mTOR/TFEB-mediated autophagy and modulating gut microbiota’ [Environmental Pollution, Maltol attenuates polystyrene nanoplastic-induced enterotoxicity by promoting AMPK/mTOR/TFEB-mediated autophagy and modulating gut microbiota, Volume 322 (2023), 121202] - Ming-hui Jin; Jun-nan Hu; Ming Zhang; Zhaojie Meng; Guo-ping Shi; Zi Wang; Wei Li (Environmental Pollution, 2023)

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Assessing tunnel basement structure damage under train excitation: Impacts of surrounding rock deterioration - Zi-Qiang Li; Kun-ping Chen; Wei-wei Huang; Jian-wen Feng; Hang Zhang; Zheng Li; Shi-jian Yang (Transportation Geotechnics, 2023)

Trade-offs between wheat soil N2O emissions and C sequestration under straw return, elevated CO2 concentration, and elevated temperature - Jing Yang; Guojun Liu; Haiyan Tian; Xin Liu; Xingyu Hao; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Aiping Wang; Ping Li; Shu Kee Lam (Science of The Total Environment, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

Reduction and adsorption of uranium(VI) from aqueous solutions using nanoscale zero-valent manganese - Xiaohan Li; Juanxi Huang; Zhengqin Shi; Yuan Xie; Zhengfan Xu; Jianyou Long; Gang Song; Yaxuan Wang; Gaosheng Zhang; Xiatiao Luo; Ping Zhang; Shuxiang Zha; et al. (Journal of Environmental Management, 2023)

Microbial colonization of microplastics in wastewater accelerates the aging process associated with oxidative stress and the insulin/IGF1 signaling pathway - Haibo Chen; Mengfan Chen; Yulun Gu; Yongqi Jiang; Ping Ding; Chen Wang; Ruolin Pan; Chongli Shi; Hui Li (Environmental Pollution, 2023)

Formation of secondary organic aerosols from the ozonolysis of Cis-3-hexenyl acetate: The effect of acidic seed particles and SO2 - Dalin Shi; Yi Chen; Jixing Liu; Gaosheng Zhao; Li Xu; Bin Jia; Ping Cheng (Atmospheric Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Study of polycyclic aromatic hydrocarbons accumulation in bioretention facilities and its influence on microbial community structure - Ya-jiao Li; Yan-ting Shi; Ling-zhi Zhao; Ya-fang Li; Jia-ping Wang; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Acute and chronic effects of sublethal neonicotinoid thiacloprid to Asian honey bee (Apis cerana cerana) - Min Shi; Yi Guo; Yan-Yan Wu; Ping-Li Dai; Shao-Jun Dai; Qing-Yun Diao; Jing Gao (Pesticide Biochemistry and Physiology, 2023)

Remediating petroleum hydrocarbons in highly saline–alkali soils using three native plant species - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yanhong Liu; Rong Ma; Ruijie Li; Leiping Shi (Journal of Environmental Management, 2023)

Enzymatic activity of 38 CYP2C9 genotypes on ibuprofen - Ling-jing Yuan; Xiang-yu Li; Feng Ye; Xin-yue Li; Qing-qing Li; Yun-shan Zhong; Shi-yu Wang; Ya-hui Wang; Guo-xin Hu; Jian-ping Cai; Jun-wei Li (Food and Chemical Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Fatigue fracture behaviour and constitutive model of freeze-thaw sandstone under multilevel fatigue loads - Zhanming Shi; Jiangteng Li; Mengxiang Wang; Jinci Chen; Hang Lin; Ping Cao (Bulletin of Engineering Geology and the Environment, 2023)

The evolution characteristics of fractures in overlying rock for underground coal fires - Yang Xiao; Qun Shi; Kun-Hua Liu; Qing-Wei Li; Zhen-Ping Wang (Bulletin of Engineering Geology and the Environment, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Photoaged microplastics induce neurotoxicity via oxidative stress and abnormal neurotransmission in zebrafish larvae (Danio rerio) - Ping Ding; Chongdan Xiang; Xintong Li; Haibo Chen; Xiaoxia Shi; Xin Li; Chushan Huang; Yunjiang Yu; Jianying Qi; Adela Jing Li; Lijuan Zhang; Guocheng Hu (Science of The Total Environment, 2023)

Prediction and mitigation analysis of railway-induced vibrations of a layered transversely isotropic ground comprising different media with a hybrid 2.5-D method - Shi-Jin Feng; Yi-Cheng Li; Jian-Ping Li (Computers and Geotechnics, 2023)

Effects of controlled-release fertilizer on N2O emissions in wheat under elevated CO2 concentration and temperature - Qi Liu; Yajing Liu; Xingyu Hao; Chunxu Song; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Ping Li (Plant and Soil, 2023)

Novel biphasic mechanism of the canonical Wnt signalling component PYGO2 promotes cardiomyocyte differentiation from hUC-MSCs - Yan Shi; Bin Qin; Xiongwei Fan; Yongqing Li; Yuequn Wang; Wuzhou Yuan; Zhigang Jiang; Ping Zhu; Jimei Chen; Yu Chen; Fang Li; Yongqi Wan; et al. (Cell and Tissue Research, 2023)
Human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) are used to regenerate the myocardium during cardiac repair after myocardial infarction. However, the regulatory mechanism underlying their ability to form mesodermal cells and differentiate into cardiomyocytes remains unclear. Here, we established a human-derived MSCs line isolated from healthy umbilical cords and established a cell model of the natural state to examine the differentiation of hUC-MSCs into cardiomyocytes. Quantitative RT-PCR, western blotting, immunofluorescence, flow cytometry, RNA Seq, and inhibitors of canonical Wnt signalling were used to detect the germ-layer markers T and MIXL1 ; the markers of cardiac progenitor cells MESP1 , GATA4 , and NKX2.5 and the cardiomyocyte-marker cTnT to identify the molecular mechanism associated with PYGO2, a key component of the canonical Wnt signalling pathway that regulates the formation of cardiomyocyte-like cells. We demonstrated that PYGO2 promotes the formation of mesodermal-like cells and their differentiation into cardiomyocytes through the hUC-MSC-dependent canonical Wnt signalling by promoting the early-stage entry of β-catenin into the nucleus. Surprisingly, PYGO2 did not alter the expression of the canonical-Wnt, NOTCH, or BMP signalling pathways during the middle–late stages. In contrast, PI3K-Akt signalling promoted hUC-MSCs formation and their differentiation into cardiomyocyte-like cells. To the best of our knowledge, this is the first study to demonstrate that PYGO2 uses a biphasic mechanism to promote cardiomyocyte formation from hUC-MSCs.

Interactions between micaceous minerals weathering and cesium adsorption - Wei Wang; Leiping Shi; Hanyu Wu; Zhe Ding; Jianjun Liang; Ping Li; Qiaohui Fan (Water Research, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Conductive materials enhance microbial salt-tolerance in anaerobic digestion of food waste: Microbial response and metagenomics analysis - Jianhao Li; Xiaofeng Xu; Cong Chen; Linji Xu; Zexuan Du; Li Gu; Ping Xiang; Dezhi Shi; Xiaoliu Huangfu; Feng Liu (Environmental Research, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Hippocampus: Molecular, Cellular, and Circuit Features in Anxiety - Hu-Jiang Shi; Shuang Wang; Xin-Ping Wang; Rui-Xin Zhang; Li-Juan Zhu (Neuroscience Bulletin, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Blood selenium level can alleviate the nephrotoxicity of lead and cadmium in the general population of the United States: a retrospective cross section analysis of population‐based nationally representative data - Yumeng Shi; Huan Hu; Zuxiang Wu; Zhiqiang Chen; Ping Li (Environmental Science and Pollution Research, 2023)

Erosion and accretion of salt marsh in extremely shallow water stages - Dezhi Chen; Jieping Tang; Fei Xing; Jun Cheng; Mingliang Li; Yiyi Zhang; Benwei Shi; Lianqiang Shi; Ya Ping Wang (Frontiers in Marine Science, 2023)
Salt marshes, which commonly exist on the upper tidal flat, provide a natural barrier against sea level rise and coastal storm. The extremely shallow water stages (water depth< 0.2 m), including the initial stage of flood tides and the last stage of ebb tides, can induce a significant impact on sediment dynamics of saltmarshes and associated tidal flats, despite lasting for only a short time (around 10 min), which has been less studied. In this study, two parallel field sites were established to quantify erosion-accretion processes and morphological changes during extremely shallow water stages in salt marshes within Doulonggang tidal flat along the Jiangsu coast. Our results revealed that obvious accretion occurred during extremely shallow water stages, with a total deposition amount of +33.8 mm in vegetated areas and +20.8 mm in unvegetated areas. In contrast, erosion dominated during deep water stages, with a total erosion amount of -22.3 mm at the vegetated site and -32.7 mm at the unvegetated site. The magnitude of bed-level change during extremely shallow water stages was 7~8 times greater than that during deep water stages, even though the duration of extremely shallow water stages was only about 14~15% of the entire tidal cycle. Furthermore, strong winds significantly impacted deposition during extremely shallow water stages compared to calm weather. During the strong wind period, the average bed level change rate reached +0.15 mm/min and +0.12 mm/min in the vegetated and unvegetated areas, respectively. This is significantly higher than the +0.05 mm/min and +0.01 mm/min during the calm weather period. These results reveal that extremely shallow water stages have substantial impacts on sedimentary processes, which are vital for the maintenance of tidal flat systems.

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Cu/ACF adsorbent modified by non-thermal plasma for simultaneous adsorption–oxidation of H2S and PH3 - Xinyu Yang; Kai Li; Chi Wang; Fei Wang; Xin Sun; Yixing Ma; Yuan Li; Lei Shi; Ping Ning (Journal of Environmental Sciences, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

An Insight into the Mechanical and Fracture Characterization of Minerals and Mineral Interfaces in Granite Using Nanoindentation and Micro X-Ray Computed Tomography - Xiu-yang Liu; Ding-ping Xu; Shao-jun Li; Shi-li Qiu; Quan Jiang (Rock Mechanics and Rock Engineering, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Quantitative Assessment of Climate Change Impacts on Forest Ecosystems - Dan Liu; Hao Yan; Cheng Long Yu; Shi Ping Yin; Cheng Wei Wang; Li Juan Gong (Forest Science, 2023)
Characterizing and predicting the response of terrestrial ecosystems to global change is part of the fundamental challenges of contemporary ecology and ecological conservation. The assessment of climate change impact on forest ecosystems has rarely used a multi-index fusion method for quantitative evaluation. We used forest distribution, net primary productivity, and vegetation coverage to establish an assessment model of the impact of climate change on forest ecosystems. We analyzed the change characteristics of these indicators in the Heilongjiang Province of China. Our results indicate the following: (1) from 2001 to 2019, the forest area in Heilongjiang Province ranged from 234,000 to 246,000 km2. The forest net primary productivity (NPP) ranged from 4.40 to 5.55 MgC·ha-1·yr-1, and the vegetation coverage ranged from 42.42% to 67.64%. The forest NPP and the vegetation coverage showed a significant upward trend. (2) The values of forest ecological roles were significantly positively correlated with the climatic potential. (3) The contribution rate of climate change to forest ecosystem change was negatively correlated with forest coverage, which varied from 4.79% to 18.07% in different regions (cities) of the province. Study Implications: Assessing the influence of climate on forest ecosystems comprehensively and accurately before the government prepares ecological measures is necessary. However, the responses of vegetation coverage and net primary productivity to climate change may not be consistent, so climate studies that consider forest ecosystem change trends by a single indicator may have confounding results. We established a model for evaluating the impact of climate change on forest ecosystems to solve this problem. This knowledge may provide a reference for the response, adaptation, and vulnerability assessment of forest ecosystems to climate change.

Effects of polyethylene and biodegradable microplastics on photosynthesis, antioxidant defense systems, and arsenic accumulation in maize (Zea mays L.) seedlings grown in arsenic-contaminated soils - Huarong Sun; Yilan Shi; Ping Zhao; Guangqiang Long; Chaohang Li; Jiajing Wang; Dan Qiu; Chunmiao Lu; Yue Ding; Lin Liu; Shuran He (Science of The Total Environment, 2023)

Physiological and transcriptome analysis of response of soybean (Glycine max) to cadmium stress under elevated CO2 concentration - Zehua Gong; Yuqian Duan; Danmei Liu; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Journal of Hazardous Materials, 2023)

Experimental and kinetic study of the effects of n-butanol addition on toluene reference fuel auto-ignition - Zhongjun Wan; Lei Shi; Dongdong Chen; Ping Li; Changhua Zhang (Fuel, 2023)

Integrative analyses of transcriptome and metabolome reveal comprehensive mechanisms of Epigallocatechin-3-gallate (EGCG) biosynthesis in response to ecological factors in tea plant (Camellia sinensis) - Ping Xiang; Qiufang Zhu; Luhuan zhang; Puzhen Xu; Lijia Liu; Yuanyuan Li; Bosi Cheng; Xingjian Wang; Jianghong Liu; Yutao Shi; Liangyu Wu; Jinke Lin (Food Research International, 2023)

Maltol attenuates polystyrene nanoplastic-induced enterotoxicity by promoting AMPK/mTOR/TFEB-mediated autophagy and modulating gut microbiota - Ming-hui Jin; Jun-nan Hu; Ming Zhang; Zhaojie Meng; Guo-ping Shi; Zi Wang; Wei Li (Environmental Pollution, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

Environmental Isotopes and Cl/Br Ratios Evidences for Delineating Arsenic Mobilization in Aquifer System of the Jianghan Plain, Central China - Yu Zhang; Qian Yu; Chongwen Shi; Ping Li; Hong Niu (Journal of Earth Science, 2023)

Early–maturing cultivar of winter wheat is more adaptable to elevated [CO2] and rising temperature in the eastern Loess Plateau - Yuanling Zhang; Shu Kee Lam; Ping Li; Yuzheng Zong; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Jing Wang (Agricultural and Forest Meteorology, 2023)

Thallium removal from wastewater using sulfidized zero-valent manganese: Effects of sulfidation method and liquid nitrogen pretreatment - Zhengqin Shi; Ping Zhang; Xiaohan Li; Yijie Zheng; Juanxi Huang; Yaxuan Wang; Xiatiao Luo; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Huosheng Li (Chemosphere, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

Effects of Reticuloendotheliosis virus on TLR-3/IFN-Β pathway in specific pathogen-free chickens - Wen-Jie Wu; Xiao-Ping Lv; Xiao-Yan Wang; Xue-Li Gao; Chao-Nan Liu; Chen-Hui Zhao; Xian-Zhe Gu; Shi-Min Zheng (Research in Veterinary Science, 2023)

Polyethylene and poly (butyleneadipate-co-terephthalate)-based biodegradable microplastics modulate the bioavailability and speciation of Cd and As in soil: Insights into transformation mechanisms - Chaohang Li; Huarong Sun; Yilan Shi; Zhengxiong Zhao; Zhen Zhang; Ping Zhao; Qiyan Gao; Xian Zhang; Bin Chen; Yongtao Li; Shuran He (Journal of Hazardous Materials, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Glucocorticoid and glycolysis inhibitors cooperatively abrogate acute graft-versus-host disease - Qi Wen; Zheng-Li Xu; Yu Wang; Meng Lv; Yang Song; Zhong-Shi Lyv; Tong Xing; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

New remains of Ailuropoda melanoleuca baconi from Yanjinggou, China: Throwing light on the evolution of giant pandas during the Pleistocene - Haiqian Hu; Haowen Tong; Qingfeng Shao; Guangbiao Wei; Haidong Yu; Jingsong Shi; Xunqian Wang; Can Xiong; Yu Lin; Ning Li; Zhaoying Wei; Ping Wang; et al. (Journal of Mammalian Evolution, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Morphological evolution of paired sand spits at the Fudu river mouth: Wave effects and anthropogenic factors - Shanhang Chi; Chi Zhang; Ping Wang; Jian Shi; Fangming Li; Yuan Li; Peng Wang; Jinhai Zheng; Jiawen Sun; Viet Thanh Nguyen (Marine Geology, 2023)

Phytostabilization mitigates antibiotic resistance gene enrichment in a copper mine tailings pond - Xinzhu Yi; Ping Wen; Jie-Liang Liang; Pu Jia; Tao-tao Yang; Shi-wei Feng; Bin Liao; Wen-sheng Shu; Jin-tian Li (Journal of Hazardous Materials, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Pyrrolizidine-producing weeds in tea gardens as an indicator of alkaloids in tea - Weiting Jiao; Luyao Wang; Lei Zhu; Tingting Shen; Taozhong Shi; Ping Zhang; Chen Wang; Hongping Chen; Xiangwei Wu; Tianyuan Yang; Qing X. Li; Rimao Hua (Food Additives & Contaminants Part B-Surveillance, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

How does dewfall affect drought assessment in different climate regions in China - Siyao Zhang; Jianzhu Li; Ting Zhang; Ping Feng; Hao Shi (Journal of Hydrology, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Pilot test of low-rank coal pyrolysis coupled with gasification to hydrogen-rich gas for direct reduced iron: Process modeling, simulation and thermodynamic analysis - Qian Liu; Ying-jie Zhao; Yi Huang; Feng Pei; Yang Cui; Li-juan Shi; Li-ping Chang; Qun Yi (Fuel, 2023)

Interacting polymer-modification enzymes in heparan sulfate biosynthesis - Tianji Zhang; Mingjia Yu; Honglian Li; Marco Maccarana; Wei Zhang; Deling Shi; Ying Kan; Xiao Zhang; Lianli Chi; Ulf Lindahl; Hongmei Li; Jin-ping Li; et al. (Carbohydrate Polymers, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

An alkali-resistant metal–organic framework as halogen bond donor for efficient and selective removing of ReO4−/TcO4− - Qing-Hua Hu; Yu-Zhen Shi; Xin Gao; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Science and Pollution Research, 2022)

A water-soluble polysaccharide from Eucommia folium: the structural characterization and anti-tumor activity in vivo - Zhi-Qian Yan; Su-Yun Ding; Pei Chen; Hui-Ping Liu; Meng-Li Chang; Shu-Yuan Shi (Glycoconjugate Journal, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Salinimicrobium sediminilitoris sp. nov., Isolated from a Tidal Flat - Cheng-Qiang Xia; Hui-Jing Niu; Kai-Shi Dong; Li Guan; Li-Ping Sun; Qin Wang; Yan-Jiao Zhang; Yi Li; Cai-Xia Pei (Current Microbiology, 2022)

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Exploring the R-ISS stage-specific regular networks in the progression of multiple myeloma at single-cell resolution - Ling Zhong; Xiao Yang; Yu Zhou; Jialing Xiao; Huan Li; Jiang Tao; Qian Xi; Chen Chu; Chenglong Li; Xi Yang; Chen Yang; Yi Zhang; et al. (Science China Life Sciences, 2022)

Transport process and mechanism of the Hongshiyan rock avalanche triggered by the 2014 Ludian earthquake, China - Shi-lin Zhang; Yue-ping Yin; Hai-bo Li; Wen-pei Wang; Jia-wen Zhou (Landslides, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

Mutation of Beclin1 acetylation site at K414 alleviates high glucose-induced podocyte impairment in the early stage of diabetic nephropathy by inhibiting hyperactivated autophagy - Jun Xu; Yujie Deng; Yingying Ke; Yunxia Zhu; Ping Wang; Qing Yu; Chengqian Li; Bimin Shi (Molecular Biology Reports, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Synthesis and anticancer activity of Boc-Gly-Pro dipeptide-annonaceous acetogenin prodrugs targeting fibroblast activation protein or other hydrolytic enzymes - Jing-Fang Shi; Ping Wu; Han-Xiang Li; Xiao-Yi Wei; Zi-Hua Jiang (Medicinal Chemistry Research, 2022)

Dynamics of nitrogen and phosphorus profile and its driving forces in a subtropical deep reservoir - Cunli Li; Ping Zhang; Guangwei Zhu; Chao Chen; Yucheng Wang; Mengyuan Zhu; Hai Xu; Cuiling Jiang; Wei Zou; Pengcheng Shi; Qing Zheng (Environmental Science and Pollution Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Leaf color formation mechanisms in Alternanthera bettzickiana elucidated by metabolite and transcriptome analyses - Wenji Li; Huigen Li; Lisha Shi; Ping Shen; Yurong Li (Planta, 2022)

Cumulative damage effect on debris slopes under frequent microseisms - Zhong-ping Yang; Shi-qi Li; Xin Tian; Yuan-xin Hu; Wan-kun Li (Journal of Mountain Science, 2022)

Influences of fisheries management measures on biological characteristics of threadfin bream (Nemipterus virgatus) in the Beibu Gulf, South China Sea - Kui Zhang; Ping Geng; Jiajun Li; Youwei Xu; Muhsan Ali Kalhoro; Mingshuai Sun; Dengfu Shi; Zuozhi Chen (Acta Oceanologica Sinica, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Synthesis and evaluation of ursolic acid-based 1,2,4-triazolo[1,5-a]pyrimidines derivatives as anti-inflammatory agents - Tian-Yi Zhang; Chun-Shi Li; Ping Li; Xue-Qian Bai; Shu-Ying Guo; Ying Jin; Sheng-Jun Piao (Molecular Diversity, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

The Mechanism of Carbonate Alkalinity Exposure on Juvenile Exopalaemon carinicauda With the Transcriptome and MicroRNA Analysis - Kunpeng Shi; Mingdong Li; Zhen Qin; Jiajia Wang; Ping Liu; Jian Li; Jitao Li (Frontiers in Marine Science, 2022)
Saline-alkali water is distributed all over the world and affects the development of fisheries. The ridge tail white prawn Exopalaemon carinicauda is an economically important shrimp in China, which has excellent environmental tolerance. However, due to its complex genetic structure, there have been few studies on its alkalinity-adaptation mechanisms. In order to explore the molecular mechanisms of E. carinicauda in adapting to the alkaline water, mRNA and miRNA transcriptomes from the gills of E. carinicauda were determined. The results showed that after alkalinity stress, the structures of the gill and hepatopancreas were disorganized; however, E. carinicauda could still maintain vital signs. Transcriptome results showed that ATP binding protein and carbonic anhydrase played an important role in alkalinity-adaptation. At the same time, a large number of immune-related genes were up-regulated, which protect E. carinicauda from bacterial infection. MiRNAs also played an important role in alkalinity-adaptation. A total of 24 miRNAs were identified as differentially expressed after alkalinity stress, and up-regulated miRNAs might active the GnRH signaling pathway and accelerate the synthesis and secretion of aldosterone, which might maintain the balance of osmotic pressure in E. carinicauda to adapt to alkaline environment. These results provide a better understanding of the alkalinity-adaptation mechanism of economic aquatic animals and provide theoretical basis for breeding in the future.

Numerical Analysis of Single-Particle Motion Using CFD-DEM in Varying-Curvature Elbows - Chao Ning; Yalin Li; Ping Huang; Hongbo Shi; Haichao Sun (Journal of Marine Science and Engineering, 2022)
Centrifugal pumps are the critical components in deep-sea mining. In order to investigate the particle motion in the curved channel of the impeller, three different types of curvature conform to blade profile to simplify the impeller design of pumps. A numerical study is conducted to investigate the flow field in a varying-curvature channel for solid-liquid two-phase flow. The flow of particles within the varying curvature channel is studied by combining the discrete element method (DEM) with computational fluid dynamics (CFD) and a comparison with Particle Image Velocimetry (PIV) test results. The results show that a polyhedral mesh with a small mesh number yields very accurate results, which makes it very suitable for CFD-DEM. Based on this method, the movement of a single particle is compared and analyzed, and the particle-motion law is obtained. The effects of the curvature ratio Cr and area ratio Ar on the motion law for a single particle are studied, and the simulation results are analyzed statistically. The results show that the effect of Cr on both the particle slip velocity and the turbulent kinetic energy only changes its strength, while the distribution law does not change significantly. Compared with the curvature ratio Cr, the area ratio Ar has a greater impact on the particles, and its distribution law becomes clearly different. As the area ratio Ar increases, the arc radius and length of the corresponding particle trajectory decrease.

Laser ablation inductively coupled plasma mass spectrometry analysis of Chinese lead-barium glass: combining multivariate kernel density estimation and maximum mean discrepancy to reinterpret the raw glass used for producing lead-barium glass - Qian Ma; Rui Wen; Yifan Yu; Long Wang; Man Li; Luwu Cai; Li Ping; Zhiqiang Zhao; Dong Wang; Xiang Wang; Ruoyu Shi; A. Mark Pollard (Archaeological and Anthropological Sciences, 2022)

Homeostasis Regulation by Potassium Channel Subfamily K Member 3 (KCNK3) in Various Fishes - Zheng-Yong Wen; Chuan-Jie Qin; Yun-Yun Lv; Yan-Ping Li; Yuan-Chao Zou; Sheng-Tao Guo; Qiong Shi (Frontiers in Marine Science, 2021)
Potassium channels are important for K + transport and cell volume regulation, which play important roles in many biological processes such as hormone secretion, ion homeostasis, excitability, and cell development. In mammals, a total of 15 potassium channels were identified and they were divided into six subfamilies, including TALK (TALK1, TALK2, TASK2), TASK (TASK1, TASK3, TASK5), TREK (TREK1, TREK2, TRAAK), TWIK (TWIK1, TWIK2, KCNK7), THIK (THIK1, THIK2) and TRESK. TASK1, also known as potassium channel subfamily k member 3 (KCNK3), is the first member identified in the TASK subfamily. This K 2 P channel has potential applications in fish breeding and aquaculture industry due to its important roles in various physiological processes. Despite its functional role has been well studied in mammals; however, it is less known in fishes. In this review, we systematically summarize recent research advances of this critical potassium channel in representative fishes, such as gene number variation, tissue distribution, phylogeny, and potential homeostasis regulation role. This paper provides novel insights into the functional properties of these fish kcnk3 genes (including osmoregulation, energy homeostasis maintenance and fatty acids metabolism regulation), and also expands our knowledge about their variations among diverse fishes.

Isoquercitrin Upregulates Aldolase C Through Nrf2 to Ameliorate OGD/R-Induced Damage in SH-SY5Y Cells - Shi-Chang Cai; Chuan-An Yi; Xiang-Shang Hu; Gen-Yun Tang; Li-Ming Yi; Xiu-Ping Li (Neurotoxicity Research, 2021)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Synergistic inhibitory effect of berberine and icotinib on non-small cell lung cancer cells via inducing autophagic cell death and apoptosis - Ping Chen; Chun-Hua Dai; Zhi-Hao Shi; Yi Wang; Jian-Nong Wu; Kang Chen; Jin-Yu Su; Jian Li (Apoptosis, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Genetic Prion Disease: Insight from the Features and Experience of China National Surveillance for Creutzfeldt-Jakob Disease - Qi Shi; Cao Chen; Kang Xiao; Wei Zhou; Li-Ping Gao; Dong-Dong Chen; Yue-Zhang Wu; Yuan Wang; Chao Hu; Chen Gao; Xiao-Ping Dong (Neuroscience Bulletin, 2021)

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Stable isotopes (δ2H) in feathers identify non-breeding origins of the endangered Jankowski’s Bunting - Zheng Han; Hai-Tao Wang; Kevin J. Kardynal; Keith A. Hobson; Wei-Ping Shang; li-shi Zhang; Yun-lei Jiang; Frédéric Jiguet (Journal of Ornithology, 2021)

Characterization of a novel shrimp pathogen, Vibrio brasiliensis , isolated from Pacific white shrimp, Penaeus vannamei - Ge Li; Guosi Xie; Hailiang Wang; Xiaoyuan Wan; Xinshu Li; Chengyin Shi; Ziyan Wang; Miao Gong; Ting Li; Ping Wang; Qingli Zhang; Jie Huang (Journal of Fish Diseases, 2021)
A novel pathogenic strain Vibrio 20190611023 was isolated from the hepatopancreas of moribund cultured Penaeus vannamei suffering from black gill disease. This strain was identified as V . brasiliensis based on the phylogenetic analyses of 16S rDNA gene and five other housekeeping genes (i.e., gapA , ftsZ , mreB , topA and gyrB ). Some biochemical features of this strain were determined with an API 20NE system, and its haemolytic activity was determined using a sheep blood agar plate. The pathogenicity of this isolate 20190611023 was confirmed by the experimental challenge tests and histopathological examinations. P. vannamei were challenged via reverse gavage with different doses of bacterial suspensions. The calculated median lethal dose (LD 50 ) was (3.16 ± 1.78) × 10 5 CFU/g (body weight). Moreover, antibiotic susceptibility tests were performed, the results of which showed that the strain 20190611023 was sensitive to chloramphenicol, compound sulphamethoxazole, ciprofloxacin, doxycycline and oxacillin, but resistant to erythromycin, kanamycin, gentamicin, cefoperazone, ceftriaxone, cefamezin and piperacillin. To our knowledge, this is the first report for demonstrating V . brasiliensis as a shrimp pathogen, which expands the host range of V . brasiliensis infection. The present study highlights that more attention should be paid to this novel pathogen in intensive shrimp aquaculture.

Two new selenite reducing bacterial isolates from paddy soil and the potential Se biofortification of paddy rice - Chunlei Huang; Helin Wang; Xinyan Shi; Yanhong Wang; Ping Li; Hanqin Yin; Yixian Shao (Ecotoxicology, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Alpha-Lipoic Acid Attenuates Cadmium- and Lead-Induced Neurotoxicity by Inhibiting Both Endoplasmic-Reticulum Stress and Activation of Fas/FasL and Mitochondrial Apoptotic Pathways in Rat Cerebral Cortex - Yan Yuan; Shi Wen Zhao; Shuang Quan Wen; Qiao Ping Zhu; Li Wang; Hui Zou; Jian Hong Gu; Xue Zhong Liu; Jian Chun Bian; Zong Ping Liu (Neurotoxicity Research, 2021)

Long non-coding RNA TPT1-AS1 sensitizes breast cancer cell to paclitaxel and inhibits cell proliferation by miR-3156-5p/caspase 2 axis - Yuan Huang; Yabing Zheng; Xiying Shao; Lei Shi; Guangliang Li; Ping Huang (Human Cell, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Co-seismic landslide mapping using Sentinel-2 10-m fused NIR narrow, red-edge, and SWIR bands - Ping Lu; Wenyang Shi; Qunming Wang; Zhongbin Li; Yuanyuan Qin; Xuanmei Fan (Landslides, 2021)

Wnt5a up-regulates Periostin through CaMKII pathway to influence periodontal tissue destruction in early periodontitis - Liu Qian; Guo Shujuan; Huang Ping; Liu Li; Shi Weiwei; Wu Yafei; Tian Weidong (Journal of Molecular Histology, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Nutrigenomics reveals potential genetic underpinning of diverse taste preference of Chinese men - Zhouhai Zhu; Junpu Mei; Silong Sun; Sheming Lu; Meng Li; Ying Guan; Ying Chen; Yuqiong Xu; Tao Zhang; Fengxue Shi; Xuemei Li; Mingming Miao; et al. (Genes & Genomics, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

The nonreciprocal heterostyly and heterotypic self-incompatibility of Ceratostigma willmottianum - Suping Gao; Wenji Li; Meiting Hong; Ting Lei; Ping Shen; Jiani Li; Mingyan Jiang; Yifan Duan; Lisha Shi (Journal of Plant Research, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Enrichment and characterization of an effective hexavalent chromium-reducing microbial community YEM001 - Yucai Lyu; Tao Yang; Herong Liu; Zheng Qi; Ping Li; Ziyao Shi; Zhen Xiang; Dachun Gong; Ning Li; Yaoping Zhang (Environmental Science and Pollution Research, 2021)

Genome-Wide Identification of Copper Stress-Regulated and Novel MicroRNAs in Mulberry Leaf - Qiuxia Du; Peng Guo; Yisu Shi; Jian Zhang; Danyan Zheng; Yang Li; Adolf Acheampong; Ping Wu; Qiang Lin; Weiguo Zhao (Biochemical Genetics, 2021)

Not vegetation itself but mis-revegetation reduces water resources - Guoyi Zhou; Jun Xia; Ping Zhou; Tingting Shi; Lin Li (Science China Earth Sciences, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Genetic diversity analysis of intraspecific hybridization between Plumbago auriculata and Plumbago auriculata f. alba based on horticultural traits and molecular markers - Xi Chen; Suping Gao; Ping Shen; Yingqi Liu; Ting Lei; Lisha Shi; Wenji Li; Yurong Li; Xiaofang Yu; Lijuan Yang; Jiani Li (Acta Physiologiae Plantarum, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

Valine acts as a nutritional signal in brain to activate TORC1 and attenuate postprandial ammonia-N excretion in Chinese perch (Siniperca chuatsi) - Jie Wang; Xu-Fang Liang; Shan He; Yan-Peng Zhang; Jiao Li; Kang Huang; Lin-Jie Shi; Ping Ren (Fish Physiology and Biochemistry, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

MdHAL3, a 4′-phosphopantothenoylcysteine decarboxylase, is involved in the salt tolerance of autotetraploid apple - Shuang Yang; Feng Zhang; Yangshu Wang; Hao Xue; Qiu Jiang; Jiajun Shi; Hongyan Dai; Zhihong Zhang; Linguang Li; Ping He; Yuanyuan Li; Yue Ma (Plant Cell Reports, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Arsenic, lead, and cadmium bioaccessibility in contaminated soils: Measurements and validations - Hong-Bo Li; Meng-Ya Li; Di Zhao; Jie Li; Shi-Wei Li; Ping Xiang; Albert L. Juhasz; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2020)

Scientific and technological power and international cooperation in the field of natural hazards: a bibliometric analysis - Jing-Li Fan; Shuo Shen; Jian-Da Wang; Shi-Jie Wei; Xian Zhang; Ping Zhong; Hang Wang (Natural Hazards, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Dynamic Risk Assessment Method of Collapse in Mountain Tunnels and Application - Sheng Wang; Li-ping Li; Shaoshuai Shi; Shuai Cheng; Huijiang Hu; Tao Wen (Geotechnical and Geological Engineering, 2020)

Lithic raw material economy at the Huayang site in Northeast China: localization and diversification as adaptive strategies in the Late Glacial - Jian-Ping Yue; You-Qian Li; Yu-Xiu Zhang; Shi-Xia Yang (Archaeological and Anthropological Sciences, 2020)
The study of lithic raw material plays an important role in developing archeologists’ understanding of the different adaptive strategies and behaviors of prehistoric people. In this paper, we present new evidence from the Huayang site that reveals lithic raw material procurement and exploitation strategies dating to around 14 ka cal. BP. The Huayang site is located in the southern portion of the Lesser Khingan Mountains in Northeast China, a key region for examining migration, diffusion, and interaction among hunter-gatherers in East and Northeast Asia. Our results indicate that diversified lithic raw materials were found and procured from local riverbeds and reduced at the site. Each raw material was reduced with distinctive knapping strategies and, as a result, there is a strong discrete spatial pattern for each of the different raw material types. Intra- and inter-site comparative analyses suggest a uniform trend towards localization and diversification of lithic raw materials in the southern Lesser Khingan Mountains, Northeast China during the Late Glacial, which seems to be associated with the paleoclimatic amelioration and the demographic expansion during this period.

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Tenuazonic acid-induced change in volatile emission from rose plants and its chemometrical analysis - Fa-zhong Yang; Yun-xian Li; Min Tang; Guo-lei Zhu; Shi-ping Zhou; Bin Yang (Journal of Plant Diseases and Protection, 2020)

Dryland agricultural environment and sustainable productivity - Gou-Xia Li; Bing-Cheng Xu; Li-Na Yin; Shi-Wen Wang; Sui-Qi Zhang; Lun Shan; Sang-Soo Kwak; Qingbo Ke; Xi-Ping Deng (Plant Biotechnology Reports, 2020)

The loess landslide on 15 march 2019 in Shanxi Province, China - Wenhui Shi; Yanrong Li; Weiwei Zhang; Jin Liu; Shengdi He; Ping Mo; Fanfan Guan (Landslides, 2020)
On 15 March 2019, a fatal deep-seated landslide occurred at the village of Zaoling in Xiangning County of Shanxi Province, China. Extending to an area of about 120 m by 85 m, with an estimated displaced mass volume of 72,000 m 3 , the landslide left 20 people dead, 13 injured, and 8 buildings destroyed. There were no precursory signals prior to the event, and usual triggering mechanisms for a landslide were absent. Investigation conducted immediately after the incident revealed that the landslide was initiated in a 1.0 to 1.5-m thick-softened layer located at 40 m depth along the contact between the loess and interbedded paleosol layer. This softened layer was highly saturated due to the perched water on top of the relatively impervious paleosol layer and became a critical weak zone since the shear strength of loess is very sensitive to water content. We suggest that the perched water originated from extensive long-term unsaturated seepage of rainwater and local rapid percolation along preferential channels such as sinkholes and root network. The Zaoling landslide confirms that unlike most landslides in non-loess areas, loess landslides can occur without identifiable triggering events. They can result from gradual build up of instability due to slow (in the span of hundred years) accumulation of deep soil water. Based on the lessons learned from this landslide event, suggestions are given for the planning of urban and rural development in loess areas. Due to the fact that the process leading to the development of such a landslide is largely concealed, further research should be aimed at gaining a more thorough understanding of the mechanism of this landslide type.

Two new phenolic glycosides from the seeds of Citrullus lanatus - Xiao-Qian Zhang; Jing Shi; Shi-Xiu Feng; Lin Xue; Li-Ping Tian (Natural Product Research, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Cloning and expression analysis of the StCUL1 gene in potato - Peng-Xiang Pang; Li Shi; Xiao-Juan Wang; Yan-Nan Chang; Yong-Ping Luo; Jin-Lin Feng; Hemu Eri; Gang Gao (Journal of Plant Biochemistry and Biotechnology, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

A challenge in anaerobic digestion of swine wastewater: recalcitrance and enhanced-degradation of dietary fibres - Zhuo Zeng; Ping Zheng; Cheng Shi; Meng Zhang; Yiyu Li; Wudi Zhang; Shengdao Shan (Biodegradation, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Influence of Different Propulsion Speeds on the Characteristics of Mine Pressure in the Fully Mechanized Caving Face During Rotary Stage - Liang Li; Xue He; Yong-qiang Chen; Ya-chun Li; Chen-hao Shi; Yu-ping Zhu (Geotechnical and Geological Engineering, 2019)

Deubiquitylatinase inhibitor b-AP15 induces c-Myc-Noxa-mediated apoptosis in esophageal squamous cell carcinoma - Beibei Sha; Xiaoyu Chen; Han Wu; Miaomiao Li; Jianxiang Shi; Longhao Wang; Xingge Liu; Ping Chen; Tao Hu; Pei Li (Apoptosis, 2019)

Comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis leaf, bud, capsule and seed crude extracts - Alyaa Nasr; Xinxin Zhou; Shi-Ping Huang; Yuan Wang; Xiaoning Li; Guo-Ping Zhu (Natural Product Research, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Recent Progress in Mercury Research by Young Chinese Scholars - Huan Zhong; Ping Li; Jianbo Shi; Jörg Rinklebe; Xinbin Feng (Bulletin of Environmental Contamination and Toxicology, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Antioxidant and α -glucosidase inhibitory ingredients identified from Jerusalem artichoke flowers - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Pema Tsering Idong; Li-Juan Mei; Yan-Duo Tao; Yan-Ping Shi (Natural Product Research, 2019)

Trivalent Chromium Supplementation Ameliorates Oleic Acid-Induced Hepatic Steatosis in Mice - Song Wang; Jian Wang; Yajing Liu; Hui Li; Qiao Wang; Zhiwei Huang; Wenbin Liu; Ping Shi (Biological Trace Element Research, 2019)

Characterization and genome analysis of novel phage vB_EfaP_IME195 infecting Enterococcus faecalis - Ronghuan Wang; Shaozhen Xing; Feiyang Zhao; Ping Li; Zhiqiang Mi; Taoxing Shi; Hui Liu; Yigang Tong (Virus Genes, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Molecular insights into brown rust resistance and potential epidemic based on the Bru1 gene in sugarcane varieties and new elite clones - Zhu Li; Ya-Chun Su; Qing Yu; Yun Chen; Shi-Wu Gao; Yong-Gang Zhang; You-Xiong Que; Li-Ping Xu (Euphytica, 2018)

The complete chloroplast genome sequence of an endangered species, Dendrobium pendulum Roxb. (Orchidaceae) - Li-Ru Wang; Shi-Qiang Wang; Jun-Feng Niu; Shang-Ping Wang; Zhe-Zhi Wang (Conservation Genetics Resources, 2018)

A New Advance Classification Method for Surrounding Rock in Tunnels Based on the Set-Pair Analysis and Tunnel Seismic Prediction System - Lin Bu; Shu-cai Li; Shao-shuai Shi; Xiao-kun Xie; Li-ping Li; Zong-qing Zhou; Zhi-jie Wen (Geotechnical and Geological Engineering, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Genomic and Transcriptomic Analysis Identified Gene Clusters and Candidate Genes for Oil Content in Peanut (Arachis hypogaea L.) - Xiaohua Wang; Ping Xu; Liang Yin; Yan Ren; Shuangling Li; Yanmao Shi; Thomas D. Alcock; Qing Xiong; Wei Qian; Xiaoyuan Chi; Manish K. Pandey; Rajeev K. Varshney; et al. (Plant Molecular Biology Reporter, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

Evolutionary relationships of two balitorids (Cypriniformes, Balitoridae) revealed by comparative mitogenomics - Li‐Xia Shi; Chen Zhang; Yin‐Ping Wang; Qiong‐Ying Tang; Patrick D. Danley; Huan‐Zhang Liu (Zoologica Scripta, 2018)
Balitoridae, a family within the Cypriniformes, inhabit torrential mountain streams in Asia. Although they have long fascinated ichthyologists for their numerous adaptations to this tumultuous environment, the evolutionary history of this group remains poorly understood. In this study, we investigate the evolutionary relationships of the balitorids with particular attention to the phylogenetic placement of two balitorid species, Yaoshania pachychulis and Erromyzon kalotaenia . Both species have extremely limited distributions, they are limited to Mt. Dayaoshan of the Pearl River in China and require dedicated conservation plans. However, little is known about their evolutionary relationships to other balitorids. Here, we examined the evolutionary relationships of Y. pachychulis and E. kalotaenia to each other and other balitorids through sequencing the complete mitochondrial genomes of nine balitorid individuals. For the newly sequenced balitorids, the length of the whole mitogenome, gene arrangement and their base composition are similar to those of other bony fishes. Analyses based on these newly sequenced mitogenomes and an additional 50 previously published mitogenomes show that Y. pachychulis and E. kalotaenia cluster as different clade within the subfamily Gastromyzontinae. The genetic distance between these two species ranges from 0.127 ± 0.003 to 0.132 ± 0.004 which is slightly higher than that between some genera (e.g. the distance between Vanmanenia and Metahomaloptera is 0.127 ± 0.004). Therefore, it is reasonable to assign Y. pachychulis and E. kalotaenia to different genera. Phylogenetic signal assessment suggested that ND 1 , ND 4 and ND 5 genes as well as their concatenated subsets perform relatively well in reconstructing the Cobitoidea phylogeny. The divergence time estimation indicated that the balitorids distributed in Mt. Dayaoshan might have originated and evolved following the flattening and uplifting of the Yunnan–Guizhou Plateau during the late Miocene to late Pliocene.

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Nonlinear analysis of the response of a single pile subjected to tension load using a hyperbolic model - Shuai Cheng; Qian-qing Zhang; Shu-cai Li; Li-ping Li; Shi-min Zhang; Kang Wang (European Journal of Environmental and Civil Engineering, 2018)

The Role of HINT1 in Methamphetamine-Induced Conditioned Place Preference - Ju-ping Li; Peng Liu; Gang Lei; Zheng Chu; Fei Liu; Chao-feng Shi; Yong-hui Dang; Teng Chen (Neurotoxicity Research, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Integrated in silico–in vitro screening of ovarian cancer peroxisome proliferator-activated receptor-γ agonists against a biogenic compound library - Gui-Lian Zhang; Feng-Ying Liu; Jing Zhang; Li-Ping Wang; Er-Xia Jia; Shi-Ming Lv (Medicinal Chemistry Research, 2018)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Effects of virus infection on plant growth, root development and phytohormone levels in in vitro-cultured pear plants - Jie Chen; Hui-Hui Tang; Liu Li; Shi-Jiao Qin; Guo-Ping Wang; Ni Hong (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Earthquake-triggered landslides by the 1718 Tongwei earthquake in Gansu Province, northwest China - Ping Sun; Rongjian Li; Hao Jiang; Ogbonnaya Igwe; Jusong Shi (Bulletin of Engineering Geology and the Environment, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Neuroprotection of dexmedetomidine against propofol-induced neuroapoptosis partly mediated by PI3K/Akt pathway in hippocampal neurons of fetal rat - Ning Zhang; Quan-ping Su; Wei-xia Zhang; Nian-jun Shi; Hao Zhang; Ling-ping Wang; Zhong-kai Liu; Ke-zhong Li (Journal of Zhejiang University-SCIENCE B, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

Overexpression of PLK3 Mediates the Degradation of Abnormal Prion Proteins Dependent on Chaperone-Mediated Autophagy - Hui Wang; Chan Tian; Jing Sun; Li-Na Chen; Yan Lv; Xiao-Dong Yang; Kang Xiao; Jing Wang; Cao Chen; Qi Shi; Qi-Xiang Shao; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Increasing the yield of middle silk gland expression system through transgenic knock-down of endogenous sericin-1 - Sanyuan Ma; Xiaojuan Xia; Yufeng Li; Le Sun; Yue Liu; Yuanyuan Liu; Xiaogang Wang; Run Shi; Jiasong Chang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Increases of Galectin-1 and its S-nitrosylated form in the Brain Tissues of Scrapie-Infected Rodent Models and Human Prion Diseases - Yan-Jun Guo; Qi Shi; Xiao-Dong Yang; Jian-Le Li; Yue Ma; Kang Xiao; Cao Chen; Jun Han; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Response of linear and cyclic electron flux to moderate high temperature and high light stress in tomato - Tao Lu; Jie-wei Shi; Zhou-ping Sun; Ming-fang Qi; Yu-feng Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

Separation of antioxidant and α -glucosidase inhibitory flavonoids from the aerial parts of Asterothamnus centrali - asiaticus - Yan-Ming Wang; Jian-Qiang Zhao; Jun-Li Yang; Yan-Duo Tao; Li-Juan Mei; Yan-Ping Shi (Natural Product Research, 2017)

Carboniferous Alaskan-type complex along the Sino–Mongolian boundary, southern margin of the Central Asian Orogenic Belt - Yuruo Shi; Linlin Li; Alfred Kröner; Jing Ding; Wei Zhang; Zengbao Huang; Ping Jian (Acta Geochimica, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Solanerioside A, an unusual 14,15-dinor-cyclophytane glucoside from the leaves of Solanum erianthum - Shi-yi Peng; Hang Li; De-po Yang; Bai Bai; Long-ping Zhu; Qin Liu; Juan Shen; Zhi-min Zhao (Natural Product Research, 2017)

The Brain NO Levels and NOS Activities Ascended in the Early and Middle Stages and Descended in the Terminal Stage in Scrapie-Infected Animal Models - Li-Na Chen; Jing Sun; Xiao-Dong Yang; Kang Xiao; Yan Lv; Bao-Yun Zhang; Wei Zhou; Cao Chen; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2017)

In vitro reprogramming of rat bmMSCs into pancreatic endocrine-like cells - Hong-Tu Li; Fang-Xu Jiang; Ping Shi; Tao Zhang; Xiao-Yu Liu; Xue-Wen Lin; Zhong-Yan San; Xi-Ning Pang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Assessment of different route choice on commuters’ exposure to air pollution in Taipei, Taiwan - Hsien-Chih Li; Pei-Te Chiueh; Shi-Ping Liu; Yu-Yang Huang (Environmental Science and Pollution Research, 2017)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Treatment of SMB-S15 Cells with Resveratrol Efficiently Removes the PrPSc Accumulation In Vitro and Prion Infectivity In Vivo - Jing Wang; Bao-Yun Zhang; Jin Zhang; Kang Xiao; Li-Na Chen; Hui Wang; Jing Sun; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

A new isocoumarin from the aerial parts of Aconitum gymnandrum - Jian-Qiang Zhao; Yan-Ming Wang; Shuo Wang; Jun Dang; Yan-Ping Shi; Li-Juan Mei; Yan-Duo Tao (Natural Product Research, 2016)

Genetic Diversity Analysis of Sugarcane Germplasm Based on Fluorescence-Labeled Simple Sequence Repeat Markers and a Capillary Electrophoresis-based Genotyping Platform - Qian You; Yong-Bao Pan; Li-Ping Xu; Shi-Wu Gao; Qin-Nan Wang; Ya-Chun Su; Yong-Qing Yang; Qi-Bin Wu; Ding-Gang Zhou; You-Xiong Que (Sugar Tech, 2016)

The Levels of Tau Isoforms Containing Exon-2 and Exon-10 Segments Increased in the Cerebrospinal Fluids of the Patients with Sporadic Creutzfeldt-Jakob Disease - Cao Chen; Wei Zhou; Yan Lv; Qi Shi; Jing Wang; Kang Xiao; Li-Na Chen; Bao-Yun Zhang; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Effect of CO 2 on Chemical and Microbial Changes of Pacific White Shrimp During Modified Atmosphere Packaging - Yun-Fang Qian; Jing Xie; Sheng-Ping Yang; Wen-Hui Wu; Qing Xiong; Zhi-Li Gao; Jian-Bing Shi (Journal of Aquatic Food Product Technology, 2016)

Identification of loci contributing to maize drought tolerance in a genome-wide association study - Nan Wang; Zhen-ping Wang; Xiao-ling Liang; Jian-feng Weng; Xiang-ling Lv; De-gui Zhang; Jie Yang; Hong-jun Yong; Ming-shun Li; Feng-hai Li; Li-yan Jiang; Shi-huang Zhang; et al. (Euphytica, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

Semi-supervised least squares support vector machine algorithm: application to offshore oil reservoir - Wei-Ping Luo; Hong-Qi Li; Ning Shi (Applied Geophysics, 2016)

Demyelination and polycythemia in a case of paraganglioma - Xin-Bao Wang; Xiu-Yu Shi; Wen-Ze Wang; Guang Yang; Li-Ping Zou (Acta Neurologica Belgica, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

Urban spring phenology in the middle temperate zone of China: dynamics and influence factors - Shouzhen Liang; Ping Shi; Hongzhong Li (International Journal of Biometeorology, 2016)

Use of flue gas desulfurization gypsum for leaching Cd and Pb in reclaimed tidal flat soil - Ping Yang; Xian Li; Ze-Jun Tong; Qu-Sheng Li; Bao-Yan He; Li-Li Wang; Shi-Hong Guo; Zhi-Min Xu (Environmental Science and Pollution Research, 2016)

On the variability of near-bed floc size due to complex interactions between turbulence, SSC, settling velocity, effective density and the fractal dimension of flocs - Yang Yang; Ya Ping Wang; Chunyan Li; Shu Gao; Benwei Shi; Liang Zhou; Dandan Wang; Gaocong Li; Chen Dai (Geo-Marine Letters, 2016)

Sediment resuspension in tidally dominated coastal environments: new insights into the threshold for initial movement - Yang Yang; Ya Ping Wang; Shu Gao; Xiao Hua Wang; Ben Wei Shi; Liang Zhou; Dan Dan Wang; Chen Dai; Gao Cong Li (Ocean Dynamics, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Global patterns and climate drivers of water‐use efficiency in terrestrial ecosystems deduced from satellite‐based datasets and carbon cycle models - Yan Sun; Shilong Piao; Mengtian Huang; Philippe Ciais; Zhenzhong Zeng; Lei Cheng; Xiran Li; Xinping Zhang; Jiafu Mao; Shushi Peng; Benjamin Poulter; Xiaoying Shi; et al. (Global Ecology and Biogeography, 2016)
Aim To investigate how ecosystem water‐use efficiency ( WUE ) varies spatially under different climate conditions, and how spatial variations in WUE differ from those of transpiration‐based water‐use efficiency ( WUE t ) and transpiration‐based inherent water‐use efficiency ( IWUE t ). Location Global terrestrial ecosystems. Methods We investigated spatial patterns of WUE using two datasets of gross primary productivity ( GPP ) and evapotranspiration ( ET ) and four biosphere model estimates of GPP and ET . Spatial relationships between WUE and climate variables were further explored through regression analyses. Results Global WUE estimated by two satellite‐based datasets is 1.9 ± 0.1 and 1.8 ± 0.6 g C m −2 mm −1 lower than the simulations from four process‐based models (2.0 ± 0.3 g C m −2 mm −1 ) but comparable within the uncertainty of both approaches. In both satellite‐based datasets and process models, precipitation is more strongly associated with spatial gradients of WUE for temperate and tropical regions, but temperature dominates north of 50° N . WUE also increases with increasing solar radiation at high latitudes. The values of WUE from datasets and process‐based models are systematically higher in wet regions (with higher GPP ) than in dry regions. WUE t shows a lower precipitation sensitivity than WUE , which is contrary to leaf‐ and plant‐level observations. IWUE t , the product of WUE t and water vapour deficit, is found to be rather conservative with spatially increasing precipitation, in agreement with leaf‐ and plant‐level measurements. Main conclusions WUE , WUE t and IWUE t produce different spatial relationships with climate variables. In dry ecosystems, water losses from evaporation from bare soil, uncorrelated with productivity, tend to make WUE lower than in wetter regions. Yet canopy conductance is intrinsically efficient in those ecosystems and maintains a higher IWUE t . This suggests that the responses of each component flux of evapotranspiration should be analysed separately when investigating regional gradients in WUE , its temporal variability and its trends.

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

Remarkable Activation of the Complement System and Aberrant Neuronal Localization of the Membrane Attack Complex in the Brain Tissues of Scrapie-Infected Rodents - Yan Lv; Cao Chen; Bao-Yun Zhang; Kang Xiao; Jing Wang; Li-Na Chen; Jing Sun; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2015)

Dengue virus infection induces formation of G3BP1 granules in human lung epithelial cells - Jun Xia; Xiaoyan Chen; Feng Xu; Yi Wang; Yongxia Shi; Yuye Li; Junfang He; Ping Zhang (Archives of Virology, 2015)

Effects of miRNA-145 on airway smooth muscle cells function - Yun Liu; Xiuzhen Sun; Yuanyuan Wu; Ping Fang; Hongyang Shi; Jing Xu; Manxiang Li (Molecular and Cellular Biochemistry, 2015)

A new highly oxygenated daphnane diterpene esters from the flower buds of Daphne genkwa - Hai-Long Jiang; Rui Wang; Jian-Yong Li; Yan-Ping Shi (Natural Product Research, 2015)

Three new phenanthrenone constituents from Trigonostemon lii - Shi-Fei Li; Hong-Ping He; Xiao-Jiang Hao (Natural Product Research, 2015)

Soil stability characteristics of mulberry lands at hydro-fluctuation belt in the Three Gorges Reservoir area, China - Ping Jiang; Dongmei Shi; Xueqin Hu; Xianzhi Huang; Yexin Li; Tianlei Guo (Environmental Monitoring and Assessment, 2015)

Molecular characterization of HbCZF1, a Hevea brasiliensis CCCH-type zinc finger protein that regulates hmg1 - Dong Guo; Hong-Yan Yi; Hui-Liang Li; Chen Liu; Zi-Ping Yang; Shi-Qing Peng (Plant Cell Reports, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Wheat acclimate to water deficit by modifying carbohydrates metabolism, water use efficiency, and growth - MengYun Hu; ZhiGang Shi; Ping Xu; Hui Li; Zhengbin Zhang (Brazilian Journal of Botany, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

Retraction Note to: Identification of gene expression profile in the rat brain resulting from acute alcohol intoxication - Ling-Yu Kong; Guang-Peng Li; Ping Yang; Wei Wu; Jin-He Shi; Xue-Liang Li; Wei-Zhen Wang (Molecular Biology Reports, 2015)

Identification and characterization of the EIN3/EIL gene family in Hevea brasiliensis - Zi-Ping Yang; Hui-Liang Li; Dong Guo; Shi-Qing Peng (Tree Genetics & Genomes, 2015)

Endophytic microbes Bacillus sp. LZR216-regulated root development is dependent on polar auxin transport in Arabidopsis seedlings - Jianfeng Wang; Yongqiang Zhang; Ying Li; Xiaomin Wang; Wenbin Nan; Yanfeng Hu; Hong Zhang; Chengzhou Zhao; Feng Wang; Ping Li; Hongyong Shi; Yurong Bi (Plant Cell Reports, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Data mining and well logging interpretation: application to a conglomerate reservoir - Ning Shi; Hong-Qi Li; Wei-Ping Luo (Applied Geophysics, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

Scrapie Infection in Experimental Rodents and SMB-S15 Cells Decreased the Brain Endogenous Levels and Activities of Sirt1 - Jing Wang; Jin Zhang; Qi Shi; Bao-Yun Zhang; Cao Chen; Li-Na Chen; Jing Sun; Hui Wang; Kang Xiao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2015)

Responses of the hepatic glutathione antioxidant defense system and related gene expression in juvenile common carp after chronic treatment with tributyltin - Zhi-Hua Li; Ping Li; Ze-Chao Shi (Ecotoxicology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Enhanced Phytoextraction of Heavy Metals from Contaminated Soil by Plant Co-cropping Associated with PGPR - Zhi-feng Liu; Hong-guang Ge; Chen Li; Zuo-ping Zhao; Feng-min Song; Shi-bin Hu (Water, Air, & Soil Pollution, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Synthesis and in vitro antiproliferative activity of novel benzisoselenazolone derivatives - Li-na Xuan; Peng Wang; Kai Zhang; Yan-ping Shi; Yu-ming Liu; Tao Zhu; Bao-quan Chen (Medicinal Chemistry Research, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Neuropeptide trefoil factor 3 attenuates naloxone-precipitated withdrawal in morphine-dependent mice - Ping Wu; Hai-Shui Shi; Yi-Xiao Luo; Ruo-Xi Zhang; Jia-Li Li; Jie Shi; Lin Lu; Wei-Li Zhu (Psychopharmacology, 2014)

RETRACTED ARTICLE: Identification of gene expression profile in the rat brain resulting from acute alcohol intoxication - Ling-Yu Kong; Guang-Peng Li; Ping Yang; Wei Wu; Jin-He Shi; Xue-Liang Li; Wei-Zhen Wang (Molecular Biology Reports, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

Unsupervised change detection based on robust chi-squared transform for bitemporal remotely sensed images - Aiye Shi; Du Q. Huynh; Feng Chen Huang; Shao Hong Shen; Wen Ping Lu; Zhen Li Ma (International Journal of Remote Sensing, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

Analysis of small RNAs derived from Chinese wheat mosaic virus - Jian Yang; Shi-Ling Zheng; Heng-Mu Zhang; Xiao-Ya Liu; Jing Li; Jun-Min Li; Jian-Ping Chen (Archives of Virology, 2014)

Isolation and characterization of LEAFY COTYLEDON 1-LIKE gene related to embryogenic competence in Citrus sinensis - Shi-ping Zhu; Jun Wang; Jun-li Ye; An-Dan Zhu; Wen-wu Guo; Xiu-xin Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

PI3K/Akt/uncoupling protein 2 signaling pathway may be involved in cell senescence and apoptosis induced by angiotensin II in human vascular endothelial cells - Ping Li; Xin Guo; Pingping Lei; Shoujun Shi; Shike Luo; Xiaoshu Cheng (Molecular Biology Reports, 2014)

Multiple correlations of mRNA expression and protein abundance in human cytokine profile - Hong-wu Du; Guang-yu Chen; Chun-he Yang; Chuan-bao Li; Yi-ping Xun; Jia Liu; Peng Chen; Li-li Shi (Molecular Biology Reports, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Neuroprotective effect of schizandrin A on oxygen and glucose deprivation/reperfusion-induced cell injury in primary culture of rat cortical neurons - Cai-Ping Wang; Gui-Cai Li; Yun-Wei Shi; Xiao-Chuan Zhang; Jian-Long Li; Zhi-Wei Wang; Fei Ding; Xin-Miao Liang (Journal of Physiology and Biochemistry, 2014)

Differential role of Rac in the basolateral amygdala and cornu ammonis 1 in the reconsolidation of auditory and contextual Pavlovian fear memory in rats - Ping Wu; Zeng-Bo Ding; Shi-Qiu Meng; Hao-Wei Shen; Shi-Chao Sun; Yi-Xiao Luo; Jian-Feng Liu; Lin Lu; Wei-Li Zhu; Jie Shi (Psychopharmacology, 2014)

Architecture and development of a multi-stage Baiyun submarine slide complex in the Pearl River Canyon, northern South China Sea - Lei Wang; Shi-Guo Wu; Qing-Ping Li; Da-Wei Wang; Shao-Ying Fu (Geo-Marine Letters, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Positive matrix factorization as source apportionment of soil lead and cadmium around a battery plant (Changxing County, China) - Jian-long Xue; Yu-you Zhi; Li-ping Yang; Jia-chun Shi; Ling-zao Zeng; Lao-sheng Wu (Environmental Science and Pollution Research, 2014)

Isolation and characterization of microsatellite markers from the Chinese endemic species, Beal’s-eyed turtle (Sacalia bealei) - Wei-ye Li; Shi-ping Gong; Liu-shuai Hua (Conservation Genetics Resources, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Cell-penetrating fusion peptides OD1 and OD2 interact with Bcr–Abl and influence the growth and apoptosis of K562 cells - Hai-xia Wang; Heng Xiao; Liang Zhong; Kun Tao; Ya-juan Li; Shi-feng Huang; Jian-ping Wen; Wen-li Feng (Molecular and Cellular Biochemistry, 2014)

Antidepressant-like effects and memory enhancement of a herbal formula in mice exposed to chronic mild stress - Xiu-Ping Sun; Si-Di Li; Zhe Shi; Teng-Fei Li; Rui-Le Pan; Qi Chang; Chuan Qin; Xin-Min Liu (Neuroscience Bulletin, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Antioxidant response and histopathological changes in brain tissue of pigeon exposed to avermectin - Ming Li; Tian-Zi You; Wen-Jun Zhu; Jian-Ping Qu; Ci Liu; Bing Zhao; Shi-Wen Xu; Shu Li (Ecotoxicology, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Syntheses and antibacterial activity of Schiff bases from 16-isopropyl-5, 9-dimethyltetracyclo [10.2.2.0 1, 10 .0 4, 9 ] hexadec-15-ene-5, 14-dicarboxylic acid - Jian Li; Jie Song; Shi-Bin Shang; Xiao-Ping Rao; Yan-Qing Gao (Natural Product Research, 2013)

Perifosine Induces Cell Apoptosis in Human Osteosarcoma Cells: New Implication for Osteosarcoma Therapy? - Chen Yao; Jian-jun Wei; Zu-yu Wang; Hui-min ding; Dong Li; Shi-chang Yan; Yong-jiang Yang; Zhang-ping Gu (Cell Biochemistry and Biophysics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Tetramethylpyrazine induces G0/G1 cell cycle arrest and stimulates mitochondrial-mediated and caspase-dependent apoptosis through modulating ERK/p53 signaling in hepatic stellate cells in vitro - Feng Zhang; De-Song Kong; Zi-Li Zhang; Na Lei; Xiao-Jing Zhu; Xiao-Ping Zhang; Li Chen; Yin Lu; Shi-Zhong Zheng (Apoptosis, 2013)

Function of the anal sacs and mid-gut in mitochondrial sulphide metabolism in the echiuran worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Li-Tao Zhang; Xiao-Li Shi; Ying-Ping Dong (Marine Biology Research, 2012)

Aggravated inflammation and increased expression of cysteinyl leukotriene receptors in the brain after focal cerebral ischemia in AQP4-deficient mice - Wen-Zhen Shi; Chun-Zhen Zhao; Bing Zhao; Qiao-Juan Shi; Li-Hui Zhang; Yan-Fang Wang; San-Hua Fang; Yun-Bi Lu; Wei-Ping Zhang; Er-Qing Wei (Neuroscience Bulletin, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Variations in soil culturable bacteria communities and biochemical characteristics in the Dongkemadi glacier forefield along a chronosequence - Guang-Xiu Liu; Ping Hu; Wei Zhang; Xiukun Wu; Xuan Yang; Tuo Chen; Manxiao Zhang; Shi-Weng Li (Folia Microbiologica, 2012)

Traditional Chinese medicines benefit to nonalcoholic fatty liver disease: a systematic review and meta-analysis - Ke-Qing Shi; Yu-Chen Fan; Wen-Yue Liu; Ling-Fei Li; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

A Highly Sensitive Fluorescent Probe for HClO and Its Application in Live Cell Imaging - Qing-Ping Zuo; Zuo-Jun Li; Yong-Hua Hu; Bin Li; Li-Hua Huang; Chun-Jiang Wang; Shi-Kun Liu; Hai-Qiang Liao (Journal of Fluorescence, 2012)

Analyses of n-alkanes degrading community dynamics of a high-temperature methanogenic consortium enriched from production water of a petroleum reservoir by a combination of molecular techniques - Lei Zhou; Kai-Ping Li; Serge Maurice Mbadinga; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Ecotoxicology, 2012)

Drug-related cues exacerbate decision making and increase craving in heroin addicts at different abstinence times - Gui-Bin Wang; Xiao-Li Zhang; Li-Yan Zhao; Li-Li Sun; Ping Wu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

EGFR-mediated G1/S transition contributes to the multidrug resistance in breast cancer cells - Shu-Jun Chen; Jing Luan; Hai-Shi Zhang; Can-Ping Ruan; Xin-Yun Xu; Qing-Quan Li; Nian-Hong Wang (Molecular Biology Reports, 2012)

Molecular characterization of a novel 14-3-3 protein gene (Hb14-3-3c) from Hevea brasiliensis - Zi-Ping Yang; Hui-Liang Li; Dong Guo; Wei-Min Tian; Shi-Qing Peng (Molecular Biology Reports, 2012)

Response of Sulfide:Quinone Oxidoreductase to Sulfide Exposure in the Echiuran Worm Urechis unicinctus - Yu-Bin Ma; Zhi-Feng Zhang; Ming-Yu Shao; Kyoung-Ho Kang; Xiao-Li Shi; Ying-Ping Dong; Jin-Long Li (Marine Biotechnology, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

A meta-analysis of HLA-DR polymorphism and genetic susceptibility to idiopathic dilated cardiomyopathy - Bo Jin; Xin-Ping Luo; Huan-Chun Ni; Wei Shen; Hai-Ming Shi; Yong Li (Molecular Biology Reports, 2012)

Central nervous system regulation of food intake and energy expenditure: role of galanin-mediated feeding behavior - Peng-Hua Fang; Mei Yu; Yin-Ping Ma; Jian Li; Yu-Mei Sui; Ming-Yi Shi (Neuroscience Bulletin, 2011)

Expression of β1,3-N-acetylglucosaminyltransferases during differentiation of human acute myeloid leukemia cells - Hao Qiu; Shi-Liang Wu; Xiang-Hong Guo; Hong-Jie Shen; Huan-Ping Zhang; Hui Li Chen (Molecular and Cellular Biochemistry, 2011)

Sequence analysis of the Meq gene in the predominant Marek’s disease virus strains isolated in China during 2006–2008 - Yan-ping Zhang; Chang-jun Liu; Feng Zhang; Weisong Shi; Jingmei Li (Virus Genes, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Microsatellite Analysis of Homozygosity Progression of Heterozygous Genotypes Segregating in the Rice Subspecies Cross Pei’ai64s/Nipponbare - Yong-shu Liang; Qi-jun Zhang; Shi-quan Wang; Li-yong Cao; Zhi-qiang Gao; Ping Li; Shi-hua Cheng (Biochemical Genetics, 2011)

Aboveground dominant functional group predicts belowground properties in an alpine grassland community of western China - Gao-Lin Wu; Wei Li; Zhi-Hua Shi; Zhou-Ping Shangguan (Journal of Soils and Sediments, 2011)

The effects of simvastatin on angiogenesis: studied by an original model of atherosclerosis and acute myocardial infarction in rabbit - Wei Shen; Hai-Ming Shi; Wei-Hu Fan; Xin-Ping Luo; Bo Jin; Yong Li (Molecular Biology Reports, 2011)

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

Application of seismic anisotropy fluid detection technology in the Ken 71 well block of Shengli Oilfield - Li-Fei Bi; Zhong-Ping Qian; Feng Zhang; Xiao-Yan Chen; Shi-Chun Han; Mark Chapman (Applied Geophysics, 2011)

The soybean GmbZIP1 transcription factor enhances multiple abiotic stress tolerances in transgenic plants - Shi-Qing Gao; Ming Chen; Zhao-Shi Xu; Chang-Ping Zhao; Liancheng Li; Hui-jun Xu; Yi-miao Tang; Xin Zhao; You-Zhi Ma (Plant Molecular Biology, 2011)

Twenty-four polymorphic microsatellite markers from spotted barbell (Hemibarbus maculates) - Jun-Jie Zhu; Shi-Li Liu; Ke-Yi Ma; Jia-Le Li; Qing-Ping Lian (Conservation Genetics Resources, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Single-step chromatography for simultaneous purification of C-phycocyanin and allophycocyanin with high purity and recovery from Spirulina (Arthrospira) platensis - Shi-Gan Yan; Li-Ping Zhu; Hai-Nan Su; Xi-Ying Zhang; Xiu-Lan Chen; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2011)

The differential behavior of arbuscular mycorrhizal fungi in interaction with Astragalus sinicus L. under salt stress - Jin Peng; Yan Li; Ping Shi; Xiuhua Chen; Hui Lin; Bin Zhao (Mycorrhiza, 2011)

A Highly Selective Fluorescent Probe for Detection of Biological Samples Thiol and Its Application in Living Cells - Qing-Ping Zuo; Bing Li; Qi Pei; Zuojun Li; Shi-Kun Liu (Journal of Fluorescence, 2010)

Leptin plays a catabolic role on articular cartilage - Jia-peng Bao; Wei-ping Chen; Jie Feng; Peng-fei Hu; Zhong-li Shi; Li-dong Wu (Molecular Biology Reports, 2010)

Cardiac matrix remodeling following intracoronary cell transplantation in dilated cardiomyopathic rabbits - Bo Jin; Xin-Ping Luo; Huan-Chun Ni; Yong Li; Hai-Ming Shi (Molecular Biology Reports, 2010)

Application of collagen-chitosan/fibrin glue asymmetric scaffolds in skin tissue engineering - Chun-mao Han; Li-ping Zhang; Jin-zhang Sun; Hai-fei Shi; Jie Zhou; Chang-you Gao (Journal of Zhejiang University-SCIENCE B, 2010)

Induction and origin of adventitious roots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Shi-Jie Chai; Li-Ping Chen; Ming-Fang Zhang; Jing-Quan Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Enhancing viability of two biocontrol yeasts in liquid formulation by applying sugar protectant combined with antioxidant - Jia Liu; Shi-Ping Tian; Bo-Qiang Li; Guo-Zheng Qin (BioControl, 2009)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

The effects of land use change on environmental quality in the red soil hilly region, China: A case study in Xianning County - Zhi-Hua Shi; Li-Ding Chen; Jun-Ping Hao; Tian-Wei Wang; Chong-Fa Cai (Environmental Monitoring and Assessment, 2009)

Differential belowground allelopathic effects of leaf and root of Mikania micrantha - Ai-Ping Wu; Hua Yu; Shu-Qin Gao; Zhen-Ying Huang; Wei-Ming He; Shi-Li Miao; Ming Dong (Trees, 2009)

A cotton (Gossypium hirsutum) DRE-binding transcription factor gene, GhDREB, confers enhanced tolerance to drought, high salt, and freezing stresses in transgenic wheat - Shi-Qing Gao; Ming Chen; Lian-Qin Xia; Hui-Jun Xiu; Zhao-Shi Xu; Lian-Cheng Li; Chang-Ping Zhao; Xian-Guo Cheng; You-Zhi Ma (Plant Cell Reports, 2009)

Arabidopsis acyl-CoA-binding proteins ACBP4 and ACBP5 are subcellularly localized to the cytosol and ACBP4 depletion affects membrane lipid composition - Shi Xiao; Hong-Ye Li; Jiao-Ping Zhang; Suk-Wah Chan; Mee-Len Chye (Plant Molecular Biology, 2008)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Plasma biochemical responses of the omnivorous crucian carp (Carassius auratus) to crude cyanobacterial extracts - Xuezhen Zhang; Ping Xie; Weimin Wang; Dapeng Li; Zechao Shi (Fish Physiology and Biochemistry, 2008)

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel - Shi-Peng Wei; Xue-Qi Li; Chu-Fang Chou; You-You Liang; Ji-Bin Peng; David G. Warnock; He-Ping Ma (The Journal of Membrane Biology, 2007)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Genetic Analysis of RET, EDNRB, and EDN3 Genes and Three SNPs in MCS + 9.7 in Chinese Patients with Isolated Hirschsprung Disease - Xian-Ning Zhang; Miao-Ni Zhou; Yun-Qing Qiu; Shi-Ping Ding; Ming Qi; Ji-Cheng Li (Biochemical Genetics, 2007)

Effect of lead on ERK activity and the protective function of bFGF in rat primary culture astroglia - Ying Zhang; Li-ping Ye; Biao Wang; Shi-cheng Cao; Li-guang Sun (Journal of Zhejiang University-SCIENCE B, 2007)

Development of EST-SSR in foxtail millet (Setaria italica) - Xiao-Ping Jia; Yun-Su Shi; Yan-Cun Song; Guo-Ying Wang; Tian-Yu Wang; Yu Li (Genetic Resources and Crop Evolution, 2007)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Highly efficient photoactivation of Mn-depleted photosystem II by imidazole-liganded manganese complexes - Bin Liu; Ping Ping Shen; Wei Shi; Yu Guang Song; Wei Li; Zhou Nie; Yang Liu (JBIC Journal of Biological Inorganic Chemistry, 2006)

Comparative blood biochemistry of Amur sturgeon, Acipenser schrenckii, and Chinese surgeon, Acipenser sinensis - Xiaotao Shi; Dapeng Li; Ping Zhuang; Fen Nie; Liangqi Long (Fish Physiology and Biochemistry, 2006)

Isolation and structure revision of 10-deacetyltaxinine from the seeds of the Chinese yew, Taxus mairei - Qing-Wen Shi; Zuo-Ping Li; Ding Zhao; Ji-Shun Gu; Hiromasa Kiyota (Natural Product Research, 2006)

Genetic diversity in the Chinese pangolin (Manis pentadactyla): Inferred from restriction enzyme analysis of mitochondrial DNAs - Ya-ping Zhang; Li-ming Shi (Biochemical Genetics, 1991)

Genetic diversity in the Chinese pangolin (Manis pentadactyla): Inferred from restriction enzyme analysis of mitochondrial DNAs - Ya-ping Zhang; Li-ming Shi (Biochemical Genetics, 1991)